Thermoplastic resin composition, production method of the same, and molded body
Patent Information
- Application Number
- JP2024145218
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-08-29
- Filing Date
- 2024-08-27
- Publication Date
- 2025-03-14
AI Technical Summary
【0013】 本開示によれば、ブタジエン単位を含むグラフト共重合体とメタクリル系共重合体とを含み、透明性、耐熱性、表面硬度、並びに、常温及び低温での耐衝撃性が良好な熱可塑性樹脂組成物を提供することができる。
Smart Images

Figure 2025036261000001 
Figure 2025036261000002 
Figure 2025036261000003
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a thermoplastic resin composition, a method for producing the same, and a molded article. [Background technology]
[0002] Examples of rubber-reinforced styrene resins include high impact polystyrene (HIPS resin), methyl methacrylate-butadiene-styrene resin (MBS resin), and acrylonitrile-butadiene-styrene resin (ABS resin). These rubber-reinforced styrene resins have transparency and are excellent in mechanical properties, moldability, electrical properties, colorability, and design properties, and are used in various applications such as miscellaneous goods, housings and parts for electrical equipment and office automation equipment, and interior and exterior components for vehicles. In general, rubber-reinforced styrene resins have good impact resistance but tend to have insufficient heat resistance. By blending a heat-resistant (meth)acrylic resin with a refractive index that matches the rubber-reinforced styrene resin, it is possible to improve heat resistance without impairing transparency.
[0003] For example, Patent Document 1 discloses a thermoplastic resin composition containing a graft copolymer (rubber-reinforced transparent resin) in which methyl methacrylate and styrene are graft-copolymerized onto a diene rubber or an acrylic rubber, and an α-methylstyrene-methyl methacrylate copolymer (Claim 1). Patent Document 2 discloses a thermoplastic resin composition containing a rubber-modified thermoplastic resin and a heat-resistant (meth)acrylic copolymer containing methacrylic acid ester units and maleimide units (claim 1). Patent Document 3 discloses a rubber-modified styrene-based resin composition containing a graft copolymer consisting of a diene-based rubber-like polymer and a styrene-methacrylic acid ester copolymer, and a (meth)acrylic copolymer consisting of (meth)acrylic acid ester units, aromatic vinyl-based monomer units, and unsaturated dicarboxylic acid anhydride units (Claim 1). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 5-279547 [Patent Document 2] JP 2001-294722 A [Patent Document 3] JP 2013-104042 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, in general, heat-resistant (meth)acrylic resins tend to have high melt viscosity. Therefore, a thermoplastic resin composition containing a rubber-reinforced styrene-based resin and a heat-resistant (meth)acrylic resin needs to be set at a relatively high temperature when melt-kneading a plurality of resins and when heating and melting the resin composition, such as when molding the resin composition. In this case, gelation may occur due to thermal degradation of the rubber-reinforced styrene-based resin. This problem may occur particularly when the rubber-reinforced styrene-based resin contains butadiene units. Gelation is undesirable because it may cause a decrease in impact resistance at low temperatures (e.g., below freezing point) and poor appearance of the molded product.
[0006] The present disclosure has been made in consideration of the above circumstances, and aims to provide a thermoplastic resin composition which contains a graft copolymer containing butadiene units and a methacrylic copolymer, and which has good transparency, heat resistance, surface hardness, and impact resistance at room temperature and low temperature. [Means for solving the problem]
[0007] The present disclosure provides the following thermoplastic resin compositions [1] to
[12] , a production method thereof, and a molded article thereof. [1] 10 to 95% by mass of a first methacrylic copolymer (A) which comprises 10 to 99% by mass of methyl methacrylate units, 1 to 40% by mass of one or more isopropenyl aromatic compound units (UI), and 0 to 60% by mass of one or more other units (UO) and has a glass transition temperature of 120 to 150°C; 5 to 40% by mass of a graft copolymer (B) obtained by graft copolymerizing a butadiene-based rubber-like polymer (BR) containing 60 to 100% by mass of butadiene units with a methacrylic copolymer (M) containing 10 to 90% by mass of methyl methacrylate units, 90 to 10% by mass of aromatic vinyl compound units, and 49 to 0% by mass of vinyl cyanide compound units; 0 to 85 mass% of a second methacrylic copolymer (C) containing 10 to 90 mass% of methyl methacrylate units, 70 to 10 mass% of aromatic vinyl compound units other than isopropenyl aromatic compound units, and 49 to 0 mass% of vinyl cyanide compound units; and an organic disulfide compound (D) of 1 to 1000 ppm, A thermoplastic resin composition satisfying the following formula (1): 0≦|n b -n m |≦0.01 (1) In the above formula, n m is defined by the following equation (2). n m =(n a ×w a +n c ×w c ) / (w a +w c ) · · · (2) In the above formula, n a , n b , n c are the refractive indices at 23°C for the sodium D line of the first methacrylic copolymer (A), the graft copolymer (B), and the second methacrylic copolymer (C), respectively. a , w b , w c are the mass ratios of the first methacrylic copolymer (A), the graft copolymer (B), and the second methacrylic copolymer (C) to the total mass of the first methacrylic copolymer (A), the graft copolymer (B), and the second methacrylic copolymer (C) in the thermoplastic resin composition, respectively. a +w b +w c =1.
[0008] [2] The thermoplastic resin composition of [1], wherein the one or more isopropenyl aromatic compound units (UI) contain an α-methylstyrene unit. [3] The thermoplastic resin composition according to [1] or [2], wherein the first methacrylic copolymer (A) contains, as the other units (UO), an aromatic vinyl compound unit other than an isopropenyl aromatic compound unit. [4] The thermoplastic resin composition according to any one of [1] to [3], wherein the first methacrylic copolymer (A) contains, as the other units (UO), one or more ring structure units (UR) selected from the group consisting of an acid anhydride unit, an imide unit having a ring structure, and a lactone ring unit.
[0009] [5] The thermoplastic resin composition according to any one of [1] to [4], wherein the butadiene-based rubbery polymer (BR) is one or more rubbery polymers selected from the group consisting of polybutadiene, copolymers containing butadiene units and aromatic vinyl compound units, and hydrogenated products thereof. [6] The thermoplastic resin composition according to any one of [1] to [5], wherein the graft copolymer (B) is a core-shell type graft copolymer particle in which at least a part of the surface of a core particle made of a butadiene-based rubber-like polymer (BR) is covered with a shell layer made of a methacrylic copolymer (M). [7] The thermoplastic resin composition according to any one of [1] to [6], wherein the one or more organic disulfide compounds (D) include di-tert-dodecyl disulfide (DDS).
[0010] [8] The thermoplastic resin composition according to any one of [1] to [7], wherein a haze value of a 3 mm-thick flat plate made of the thermoplastic resin composition, measured in accordance with JIS K7136, is 0 to 10%. [9] The thermoplastic resin composition according to any one of [1] to [8], wherein a test piece made of the thermoplastic resin composition and having a length of 80 mm, a width of 10 mm and a thickness of 4 mm has a deflection temperature under load of 85 to 120°C, as measured in accordance with JIS K7191.
[10] A test piece made of the thermoplastic resin composition and having a length of 80 mm, a width of 10 mm, and a thickness of 4 mm is provided with a notch having a tip radius of 0.25 mm and a depth of 2 mm, and the Charpy impact strength measured at -30°C in accordance with JIS K7111 is 4 to 15 kJ / m 2 The thermoplastic resin composition according to any one of [1] to [9],
[0011]
[11] A step (S1) of producing an organic disulfide compound-added methacrylic copolymer (AD) containing a first methacrylic copolymer (A) and an organic disulfide compound (D); A method for producing a thermoplastic resin composition according to any one of [1] to
[10] , comprising a step (S2) of melt-kneading 10 to 95 mass% of an organic disulfide compound-added methacrylic copolymer (AD), 5 to 40 mass% of a graft copolymer (B), and 0 to 85 mass% of a second methacrylic copolymer (C).
[0012]
[12] A molded article comprising the thermoplastic resin composition according to any one of [1] to
[10] . Effect of the Invention
[0013] According to the present disclosure, it is possible to provide a thermoplastic resin composition which contains a graft copolymer containing butadiene units and a methacrylic copolymer, and which has good transparency, heat resistance, surface hardness, and impact resistance at room temperature and low temperature. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] In this specification, unless otherwise specified, a "unit" contained in a polymer is a repeating unit contained in the polymer, and is a monomer unit derived from a raw material monomer or a derived unit derived from one or more types of monomer units. In this specification, (meth)acrylic is a general term for acrylic and methacrylic, and the same applies to (meth)acrylonitrile and the like.
[0015] [Thermoplastic resin composition] The thermoplastic resin composition of the present disclosure contains a first methacrylic copolymer (A) consisting of 10 to 99 mass% of methyl methacrylate (MMA) units, 1 to 40 mass% of one or more isopropenyl aromatic compound units (UI), and 0 to 60 mass% of one or more other units (UO). The thermoplastic resin composition of the present disclosure further contains a graft copolymer (B) obtained by graft copolymerizing a butadiene-based rubbery polymer (BR) containing 60 to 100 mass% of butadiene units with a methacrylic copolymer (M) containing 10 to 90 mass% of methyl methacrylate (MMA) units, 90 to 10 mass% of one or more aromatic vinyl compound units, and 49 to 0 mass% of one or more vinyl cyanide compound units. The thermoplastic resin composition of the present disclosure may further include a second methacrylic copolymer (C) containing 10 to 90 mass% of methyl methacrylate (MMA) units, 70 to 10 mass% of aromatic vinyl compound units other than isopropenyl aromatic compound units, and 49 to 0 mass% of vinyl cyanide compound units. In the thermoplastic resin composition of the present disclosure, the content of the first methacrylic copolymer (A) is 10 to 95 mass%, the content of the graft copolymer (B) is 5 to 40 mass%, and the content of the second methacrylic copolymer (C) is 0 to 85 mass%.
[0016] (Organic disulfide compounds (D)) The thermoplastic resin composition of the present disclosure contains one or more organic disulfide compounds (D) as an additive in an amount of 1 to 1000 ppm. The lower limit is preferably 10 ppm, more preferably 20 ppm, even more preferably 50 ppm, particularly preferably 70 ppm, and most preferably 100 ppm. The upper limit is preferably 800 ppm, more preferably 750 ppm, even more preferably 700 ppm, even more preferably 650 ppm, particularly preferably 600 ppm, and most preferably 550 ppm.
[0017] As explained in the section of [Background Art], heat-resistant (meth)acrylic resins generally tend to have high melt viscosity. Therefore, it is necessary to set a relatively high temperature when the thermoplastic resin composition containing a rubber-reinforced styrene-based resin and a heat-resistant (meth)acrylic resin is heated and melted during melt-kneading of multiple resins and molding of the resin composition. In this case, gelation may occur due to thermal degradation of the rubber-reinforced styrene-based resin. This problem may occur particularly when the rubber-reinforced styrene-based resin contains butadiene units. It is considered that gelation occurs due to a crosslinking reaction between alkyl radicals under high-temperature heating. Gelation is undesirable because it can cause a decrease in impact resistance at low temperatures (e.g., below freezing point) and poor appearance of molded products.
[0018] According to the research of the present inventors, it has been found that in the thermoplastic resin composition of the present disclosure containing an appropriate amount of the organic disulfide compound (D), the presence of an appropriate amount of the organic disulfide compound (D) effectively suppresses thermal deterioration and thermal decomposition of each copolymer during heating and melting during production of the resin composition and molding processing, etc. In the thermoplastic resin composition of the present disclosure containing an appropriate amount of organic disulfide compound (D), thermal deterioration of the graft copolymer (B) containing butadiene units is suppressed, and gelation of the graft copolymer (B) containing butadiene units can be effectively suppressed during heat melting during production of the resin composition and during molding processing, etc. As a result of effectively suppressing thermal deterioration of the graft copolymer (B) containing butadiene units and the resulting gelation, a thermoplastic resin composition having excellent impact resistance at room temperature (20 to 25°C) and low temperatures (e.g., below freezing point) can be stably produced.
[0019] In the thermoplastic resin composition of the present disclosure containing an appropriate amount of organic disulfide compound (D), even if the residence time in a heated and molten state is long during the production of the resin composition, during molding, etc., foaming due to thermal decomposition of each copolymer and poor appearance due to gelation of the graft copolymer (B) containing butadiene units can be suppressed. In the thermoplastic resin composition of the present disclosure containing an appropriate amount of organic disulfide compound (D), discoloration such as yellowing and odor can be suppressed during the production of the resin composition, during molding, etc., during the heat melting.
[0020] It is considered that the organic disulfide compound (D) can effectively suppress the thermal degradation and thermal decomposition of each copolymer by using thiyl radicals generated by cleavage of disulfide bonds to effectively capture alkyl radicals generated by thermal degradation or thermal decomposition of each copolymer.
[0021] For example, the action and effect of the organic disulfide compound (D) on the methacrylic copolymer (A) is presumed to be as follows. In general, it is known that isopropenyl aromatic compounds such as αMSt have a low ceiling temperature, which is the temperature at which the polymerization reaction rate and the depolymerization reaction rate become equal. For example, the ceiling temperature of αMSt is 61°C. In general, a copolymer containing a monomer unit having a methyl group at the α-position such as MMA unit and an isopropenyl aromatic compound unit can suppress the isopropenyl aromatic compound chain in which repeating units of the isopropenyl aromatic compound are lined up by performing polymerization at a temperature higher than the ceiling temperature of the isopropenyl aromatic compound, but tends to contain a certain amount of this chain. During the production of resin, during the production of resin composition, and during heating and melting during molding, etc., depolymerization type decomposition starting from this isopropenyl aromatic compound chain occurs, so that methacrylic copolymers containing MMA units and isopropenyl aromatic compound units (UI) such as αMSt units tend to have a relatively low thermal decomposition temperature. When an appropriate amount of the organic disulfide compound (D) is present during the production of a resin, the production of a resin composition, and the heating and melting during molding or other processing, it is presumed that the thiyl radical generated by the cleavage of a disulfide bond stabilizes the alkyl radical generated by depolymerization starting from the isopropenyl aromatic compound chain, thereby significantly improving the thermal decomposition resistance.
[0022] For the reasons described above, the thermoplastic resin composition of the present disclosure and a molded article containing the thermoplastic resin composition of the present disclosure can have excellent heat resistance and thermal decomposition resistance (thermal stability); mechanical properties such as surface hardness and impact resistance at room temperature and low temperature; moldability; and appearance.
[0023] Examples of the organic disulfide compound (D) include diethyl disulfide, di-n-propyl disulfide, di-n-butyl disulfide, di-sec-butyl disulfide, di-tert-butyl disulfide, di-n-amyl disulfide, di-tert-amyl disulfide, di-tert-hexyl disulfide, di-n-octyl disulfide, di-tert-octyl disulfide, di-n-dodecyl disulfide, di-tert-dodecyl disulfide (DDS), di-n-stearin disulfide, ethyl-n-propyl disulfide, ethyl-tert-butyl disulfide, ethyl-sec-butyl disulfide, and n-propyl- Examples of the dialkyl disulfide compounds include isopropyl disulfide; aromatic disulfide compounds such as diphenyl disulfide, dibenzyl disulfide (DBS), and di-p-tolyl disulfide; cyclic disulfide compounds such as ditrimethylene disulfide, ditetramethylene disulfide, and dicyclohexyl disulfide; amino group-containing disulfide compounds such as cystine and diaminodiphenyl disulfide; disulfides of carboxylic acids or derivatives thereof such as dithiodiclycolic acid, dithiodipropionic acid, and dithiodiclycolic acid-2-ethylhexyl; and unsaturated bond-containing disulfide compounds such as diallyl disulfide. Among them, dialkyl disulfide compounds and / or aromatic disulfide compounds are preferred. From the viewpoint of the cleavage temperature of the disulfide bond, the dialkyl disulfide compound is preferably a di-tert-alkyl disulfide such as di-tert-dodecyl disulfide (DDS). The aromatic disulfide compound is preferably dibenzyl disulfide (DBS) or the like. The timing of adding the organic disulfide compound (D) is not particularly limited, and may be any timing, such as before, during, or after the polymerization of the first methacrylic copolymer (A), the graft copolymer (B), or the second methacrylic copolymer (C), and during the production of the thermoplastic resin composition.
[0024] (Refractive index relationship) The thermoplastic resin composition of the present disclosure satisfies the following formula (1). 0≦|n b -nm |≦0.01 (1) In the above formula, n m is defined by the following equation (2). n m =(n a ×w a +n c ×w c ) / (w a +w c ) · · · (2) In the above formula, n a , n b , n c are the refractive indices at 23°C for the sodium D line of the first methacrylic copolymer (A), the graft copolymer (B), and the second methacrylic copolymer (C), respectively. a , w b , w c are the mass ratios of the first methacrylic copolymer (A), the graft copolymer (B), and the second methacrylic copolymer (C) to the total mass of the first methacrylic copolymer (A), the graft copolymer (B), and the second methacrylic copolymer (C) in the thermoplastic resin composition, respectively. a +w b +w c =1.
[0025] n m is the average refractive index of the matrix resin composed of the first methacrylic copolymer (A) and the second methacrylic copolymer (C) which may be contained as an optional component. |n b -n m | is the difference between the refractive index of the graft copolymer (B) which is the rubber component and the average refractive index of the matrix resin (also referred to as the refractive index difference (Δn)). When the refractive index difference (Δn) is 0.01 or less, the thermoplastic resin composition of the present disclosure can have high transparency because light scattering at the boundary between the matrix resin and the rubber component is reduced. The refractive index difference (Δn) is preferably small, and the upper limit is preferably 0.008, more preferably 0.005, further preferably 0.003, particularly preferably 0.002, and most preferably 0.001. The ideal value of the refractive index difference (Δn) is 0.
[0026] As long as the above formula (1) is satisfied, the refractive index (n) of each copolymer is not particularly limited. The refractive index (n a ) can be, for example, 1.500 to 1.570. The lower limit is more preferably 1.505, particularly preferably 1.510, and most preferably 1.515. The upper limit is preferably 1.560, more preferably 1.550, even more preferably 1.540, particularly preferably 1.530, and most preferably 1.520. The refractive index (n b ) can be, for example, 1.500 to 1.570. The lower limit is more preferably 1.505, particularly preferably 1.510, and most preferably 1.515. The upper limit is preferably 1.560, more preferably 1.550, even more preferably 1.540, particularly preferably 1.530, and most preferably 1.520. The refractive index (n c ) can be, for example, 1.500 to 1.570. The lower limit is more preferably 1.505, particularly preferably 1.510, and most preferably 1.515. The upper limit is preferably 1.560, more preferably 1.550, even more preferably 1.540, particularly preferably 1.530, and most preferably 1.520. |n a -n b is not particularly limited, the smaller the better, and is preferably 0 to 0.01. The upper limit is preferably 0.008, more preferably 0.005, and even more preferably 0.003. a -n c | and |n b -n c The preferred range of | is |n a -n bSame as |.
[0027] The refractive index of the methacrylic copolymers (A) and (C) mainly depends on the unit composition of the copolymer, and therefore the refractive index of the methacrylic copolymers (A) and (C) can be adjusted to a desired range by adjusting the raw material monomer composition. The refractive index of the methacrylic copolymers (A) and (C) can be estimated from the refractive index of the homopolymer of each monomer and the mass ratio of each monomer. For example, the refractive index (n XYZ The theoretical value of can be expressed by the following formula: n XYZ =n X ×w X +n Y ×w Y +n Z ×w Z In the above formula, n X , n Y , n Z are the refractive indices of the homopolymer of monomer X, the homopolymer of monomer Y, and the homopolymer of monomer Z, respectively. X , w Y , w Z are the mass fractions of monomer X, monomer Y, and monomer Z in the copolymer, respectively. X +w Y +w Z =1.
[0028] The refractive index of the graft copolymer (B) can be adjusted to a desired range by adjusting the unit composition of the butadiene rubber polymer (BR) and / or the raw material monomer composition of the methacrylic copolymer (M) which is the graft chain. The refractive index of the graft copolymer (B) can also be estimated from the unit composition of the butadiene rubber polymer (BR) and the unit composition of the methacrylic copolymer (M) which is the graft chain, like the refractive indexes of the methacrylic copolymers (A) and (C).
[0029] The average refractive index (n m ), and the refractive index (n b ) can be measured as follows: A solvent that dissolves the matrix resin composed of the first methacrylic copolymer (A) and the second methacrylic copolymer (C) that may be included as an optional component is added to the thermoplastic resin composition of the present disclosure to dissolve the matrix resin. The resulting cloudy solution is separated into a solvent-soluble component and a solvent-insoluble component by an operation such as centrifugation. The soluble component (matrix resin) and the insoluble component (graft copolymer (B)) are each purified, and the refractive index is measured. In this specification, unless otherwise specified, the "refractive index" refers to the refractive index for sodium D lines at 23° C., and is determined by the method described in the Examples section below.
[0030] (Physical Properties) The thermoplastic resin composition of the present disclosure can have excellent transparency. The haze value of a 3 mm thick plate made of the thermoplastic resin composition of the present disclosure, measured in accordance with JIS K7136, can be 0 to 10%. The upper limit is preferably 7%, more preferably 5%, and particularly preferably 4%. The lower limit can be, for example, 0.1%, 0.5%, or 1%.
[0031] The thermoplastic resin composition of the present disclosure can have excellent heat resistance and rigidity even under load. The deflection temperature under load (HDT) of a test piece of the thermoplastic resin composition of the present disclosure, having a length of 80 mm, a width of 10 mm, and a thickness of 4 mm, measured in accordance with JIS K7191, can be, for example, 85°C or higher. The lower limit is preferably 88°C, more preferably 90°C, particularly preferably 95°C, and most preferably 100°C. The upper limit is not particularly limited and is, for example, 120°C or 110°C.
[0032] The thermoplastic resin composition of the present disclosure can have excellent impact resistance at room temperature and low temperature. A test piece made of the thermoplastic resin composition of the present disclosure and having a length of 80 mm, a width of 10 mm, and a thickness of 4 mm is provided with a notch having a tip radius of 0.25 mm and a depth of 2 mm, and the Charpy impact strength measured at room temperature (23±2°C) in accordance with JIS K7111 is, for example, 4 kJ / m 2 The lower limit is preferably 4.5 kJ / m 2 , more preferably 5 kJ / m 2 The upper limit is not particularly limited, and is, for example, 25 kJ / m 2 , 20kJ / m 2 , or 15 kJ / m 2 It is. A test piece made of the thermoplastic resin composition of the present disclosure and having a length of 80 mm, a width of 10 mm, and a thickness of 4 mm is provided with a notch having a tip radius of 0.25 mm and a depth of 2 mm, and the Charpy impact strength measured at -30°C in accordance with JIS K7111 is, for example, 4 kJ / m 2 The upper limit is not particularly limited, and may be, for example, 15 kJ / m 2 , 10kJ / m 2 , or 8 kJ / m 2 It is. For specific evaluation methods of the haze value, the deflection temperature under load (HDT), and the Charpy impact strength, please refer to the section [Examples] below.
[0033] (First methacrylic copolymer (A)) The content of the first methacrylic copolymer (A) in the thermoplastic resin composition of the present disclosure is 10 to 95% by mass. The lower limit is preferably 15% by mass, more preferably 20% by mass, even more preferably 30% by mass, particularly preferably 40% by mass, and most preferably 50% by mass. The upper limit is preferably 90% by mass, more preferably 88% by mass, and particularly preferably 85% by mass. When the content of the first methacrylic copolymer (A) in the thermoplastic resin composition of the present disclosure is equal to or more than the above lower limit, the thermoplastic resin composition can have excellent heat resistance and surface hardness, and when the content of the first methacrylic copolymer (A) is equal to or less than the above upper limit, the thermoplastic resin composition can have excellent impact resistance.
[0034] The first methacrylic copolymer (A) contains methyl methacrylate (MMA) units and one or more isopropenyl aromatic compound units (UI), and may further contain one or more other units (UO).
[0035] The content of MMA units in the first methacrylic copolymer (A) is 10 to 99% by mass. The lower limit is preferably 20% by mass, more preferably 30% by mass, even more preferably 40% by mass, even more preferably 50% by mass, even more preferably 55% by mass, particularly preferably 60% by mass, and most preferably 65% by mass. The upper limit is preferably 95% by mass, more preferably 90% by mass, particularly preferably 85% by mass, and most preferably 80% by mass.
[0036] The content of one or more isopropenyl aromatic compound units (UI) in the first methacrylic copolymer (A) (unless otherwise specified, the total amount when there are multiple types) is 1 to 40 mass%. The lower limit is preferably 5 mass%, more preferably 10 mass%, and particularly preferably 15 mass%. The upper limit is preferably 35 mass%, more preferably 30 mass%, particularly preferably 25 mass%, and most preferably 20 mass%.
[0037] If the content of the isopropenyl aromatic compound unit (UI) is less than the lower limit, the heat resistance of the first methacrylic copolymer (A) may be insufficient. If the content of the isopropenyl aromatic compound unit (UI) is more than the upper limit, the polymerizability, thermal decomposition resistance, and moldability of the first methacrylic copolymer (A) may be reduced. If the content of the isopropenyl aromatic compound unit (UI) is more than the upper limit, it becomes difficult to control the copolymerization of the isopropenyl aromatic compound (I), and it may be difficult to stably produce the first methacrylic copolymer (A) having a uniform composition, such as the content of the isopropenyl aromatic compound unit (UI). Variation in the composition, such as the content of the isopropenyl aromatic compound unit (UI), may lead to a decrease in heat resistance and mechanical properties, such as rigidity and surface hardness.
[0038] If the content of MMA unit and the content of isopropenyl aromatic compound unit (UI) are within the above ranges, the first methacrylic copolymer (A) can have good transparency, heat resistance, thermal decomposition resistance, polymerizability, and moldability. In addition, if the content of MMA unit and the content of isopropenyl aromatic compound unit (UI) are within the above ranges, the first methacrylic copolymer (A) can be relatively easily controlled in copolymerization of isopropenyl aromatic compound (I), and the first methacrylic copolymer (A) having a uniform composition such as the content of isopropenyl aromatic compound unit (UI) can be stably produced, and the first methacrylic copolymer (A) having good heat resistance and mechanical properties such as rigidity and surface hardness can be stably produced.
[0039] The first methacrylic copolymer (A) is obtained by copolymerizing methyl methacrylate (MMA), one or more isopropenyl aromatic compounds (I), and, if necessary, one or more other monomers (O). Examples of the isopropenyl aromatic compound (I) include alkyl-substituted isopropenylbenzenes such as isopropenylbenzene (α-methylstyrene (αMSt)), isopropenylnaphthalene, isopropenyltoluene, isopropenylethylbenzene, isopropenylpropylbenzene, isopropenylbutylbenzene, isopropenylpentylbenzene, isopropenylhexylbenzene, and isopropenyloctylbenzene. From the viewpoint of availability of raw materials, etc., the one or more isopropenyl aromatic compounds (I) preferably contain one or more alkyl-substituted isopropenylbenzenes, and particularly preferably contain isopropenylbenzene (α-methylstyrene (αMSt)).
[0040] The other monomer (O) may be a vinyl monomer (V) having one polymerizable unsaturated bond in one molecule other than methyl methacrylate (MMA) and the isopropenyl aromatic compound (I). Examples of the vinyl monomer (V) include (meth)acrylic acid esters other than MMA, such as methyl acrylate; (meth)acrylic acid alkyl esters such as ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate; (meth)acrylic acid aryl esters such as phenyl (meth)acrylate; and (meth)acrylic acid cycloalkyl esters such as cyclohexyl (meth)acrylate and norbornenyl (meth)acrylate. Other examples of the vinyl monomer (V) include (meth)acrylic acid, (meth)acrylamide, and (meth)allylonitrile. Other examples of the vinyl monomer (V) include aromatic vinyl compounds other than the isopropenyl aromatic compound (I), such as styrene (St); alkyl-substituted styrenes such as o-, m-, or p-methylstyrene, 2,4-dimethylstyrene, 2,5-dimethylstyrene, 3,4-dimethylstyrene, 3,5-dimethylstyrene, o-, m-, or p-ethylstyrene; and 1,1-diphenylethylene. From the viewpoints of melt flowability and productivity of the first methacrylic copolymer (A), styrene (St) and the like are preferred.
[0041] The first methacrylic copolymer (A) may contain, as one or more other units (UO), one or more ring structural units (UR) selected from the group consisting of an acid anhydride unit, an imide unit containing a ring structure, and a lactone ring unit, instead of or in addition to the aromatic vinyl compound unit other than the isopropenyl aromatic compound unit. The methacrylic copolymer (A) containing the ring structural unit (UR) has high heat resistance and is therefore preferred.
[0042] The first methacrylic copolymer (A) having no ring structural unit (UR) in the main chain can be produced by copolymerizing a monomer mixture containing methyl methacrylate (MMA) and one or more isopropenyl aromatic compounds (I) and, if necessary, one or more other monomers (O) by a known method. Examples of a method for producing the first methacrylic copolymer (A) having a ring structural unit (UR) in the main chain include a method for copolymerizing, by a known method, a plurality of monomers including methyl methacrylate (MMA), one or more isopropenyl aromatic compounds (I), raw monomers for the ring structural unit (UR), and other monomers as necessary; and a method for copolymerizing, by a known method, a methacrylic copolymer containing MMA units and one or more isopropenyl aromatic compound units (UI) but no ring structural unit (UR), and then introducing a ring structure into the main chain to form the ring structural unit (UR). Examples of the polymerization method for the methacrylic copolymer include radical polymerization methods such as (continuous) bulk polymerization method, suspension polymerization method, solution polymerization method, and emulsion polymerization method; and anionic polymerization method.
[0043] The content of the ring structural unit (UR) in the first methacrylic copolymer (A) (the total amount when there are multiple types, unless otherwise specified) is 0 to 60% by mass. The lower limit is preferably 5% by mass. The upper limit is preferably 55% by mass, more preferably 50% by mass, even more preferably 40% by mass, particularly preferably 30% by mass, and most preferably 20% by mass.
[0044] Examples of the acid anhydride unit include a maleic anhydride (Mah) unit, a glutaric anhydride unit, and an itaconic anhydride unit, with the maleic anhydride (Mah) unit being preferred. Examples of the imide unit containing a ring structure include an unsubstituted or N-substituted glutarimide unit and an unsubstituted or N-substituted maleimide unit.
[0045] The glutarimide (GI) unit is a unit having an unsubstituted or N-substituted 2,6-dioxopiperidinediyl structure, and examples thereof include units represented by the following general formula (I).
[0046] [ka] (I)
[0047] In formula (I), two R 1are each independently a hydrogen atom or a methyl group, and two R 1 Preferably, both R are methyl groups. 2 represents a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, or an organic group containing an aromatic ring and having 6 to 15 carbon atoms, and is preferably a hydrogen atom, a methyl group, an n-butyl group, a cyclohexyl group, or a benzyl group, more preferably a methyl group, an n-butyl group, or a cyclohexyl group, and particularly preferably a methyl group.
[0048] The first methacrylic copolymer (A) containing glutarimide (GI) units can have properties such as a high glass transition temperature (Tg), good impact resistance, and good dimensional and shape stability against temperature. The first methacrylic copolymer (A) containing glutarimide (GI) units can be produced by known methods described in, for example, WO 2005 / 108438, JP 2010-254742 A, JP 2008-273140 A, and JP 2008-274187 A.
[0049] A method for producing the first methacrylic copolymer (A) containing glutarimide (GI) units includes a method including an imide cyclization reaction step in which an imidization agent is added to a precursor resin having two adjacent methyl methacrylate (MMA) units and reacted. Examples of the imidization agent include ammonia; aliphatic hydrocarbon group-containing amines such as methylamine (also called monomethylamine), ethylamine, diethylamine, n-propylamine, isopropylamine, n-butylamine, isobutylamine, t-butylamine, and n-hexylamine; aromatic hydrocarbon group-containing amines such as aniline, toluidine, trichloroaniline, and n-methylbenzylamine; alicyclic hydrocarbon group-containing amines such as cyclohexylamine and n-methylcyclohexylamine; urea compounds such as urea, 1,3-dimethylurea, 1,3-diethylurea, and 1,3-dipropylurea. Among them, methylamine and the like are preferred.
[0050] The unsubstituted or N-substituted maleimide unit is a unit having an unsubstituted or N-substituted 2,5-pyrrolidinedione structure, and examples thereof include a unit represented by the following formula (II) (also referred to as a maleimide unit (II)).
[0051] [ka] (II)
[0052] In formula (II), two R 11 are each independently a hydrogen atom or a methyl group, and two R 11 Preferably, both R are methyl groups. 12 represents a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, or an organic group containing an aromatic ring and having 6 to 15 carbon atoms, and is preferably a methyl group, an n-butyl group, a cyclohexyl group, or a benzyl group, more preferably a methyl group, an n-butyl group, or a benzyl group, and particularly preferably a methyl group.
[0053] The method for producing the first methacrylic copolymer (A) containing maleimide units includes a method of polymerizing a monomer mixture containing a monomer containing a maleimide unit, a method of reacting a maleic anhydride unit in a polymerization reaction product of a monomer mixture containing maleic anhydride with an imidizing agent, etc. For the latter method, see JP-B-61-026924, JP-B-7-042332, JP-A-9-100322, and JP-A-2001-329021.
[0054] Examples of monomers containing maleimide units include N-alkylmaleimides such as N-methylmaleimide, N-ethylmaleimide, N-butylmaleimide, and N-cyclohexylmaleimide (ChMI); and N-arylmaleimides such as N-phenylmaleimide (PhMI), N-methylphenylmaleimide, and N-chlorophenylmaleimide. N-cyclohexylmaleimide (ChMI), N-phenylmaleimide (PhMI), and the like are preferred.
[0055] The lactone ring unit is a unit containing a >CH-OC(=O)- group in the ring structure. The unit containing a >CH-OC(=O)- group in the ring structure preferably has 4 to 8 ring constituent elements, more preferably 5 to 6, and most preferably 6. Examples of the unit containing a >CH-OC(=O)- group in the ring structure include lactone diyl units such as β-propiolactone diyl unit, γ-butyrolactone diyl unit, and δ-valerolactone diyl unit. In the formula, ">C" means that the carbon atom C has two bonds.
[0056] For example, an example of the δ-valerolactonediyl unit is a unit represented by the following formula (III) (also referred to as a lactone ring unit (III)).
[0057] [ka] (III)
[0058] In formula (III), R 21 , R 22 , and R 23 are each independently a hydrogen atom or an organic group having 1 to 20 carbon atoms, preferably a hydrogen atom or an organic group having 1 to 10 carbon atoms, more preferably a hydrogen atom or an organic group having 1 to 5 carbon atoms. Here, the organic group is not particularly limited as long as it has 1 to 20 carbon atoms, and examples thereof include a linear or branched alkyl group, a linear or branched aryl group, a -OCOCH3 group, and a -CN group. The organic group may contain a heteroatom such as an oxygen atom. Preferably, R 22 is a methyl group, and R 21 and R 23 is a hydrogen atom.
[0059] The lactone ring unit can be obtained by intramolecular cyclization of a hydroxy group and an ester group, for example, by intramolecular cyclization of a 2-(hydroxyalkyl)acrylic acid ester unit and a methyl (meth)acrylate unit. See JP-A-2000-230016, JP-A-2001-151814, JP-A-2002-120326, JP-A-2002-254544, and JP-A-2005-146084.
[0060] The glutaric anhydride unit is a unit having a 2,6-dioxodihydropyrandiyl structure, and examples thereof include a unit represented by the formula (IV) (also referred to as a glutaric anhydride unit (IV)).
[0061] [ka] (IV)
[0062] In formula (IV), two R 31 are each independently a hydrogen atom or an alkyl group having 1 to 5 carbon atoms, and are preferably a methyl group.
[0063] The glutaric anhydride unit can be obtained by intramolecular cyclization of two adjacent (meth)acrylic acid units, or intramolecular cyclization of a (meth)acrylic acid unit and a methyl (meth)acrylate unit, etc. See JP-A-2007-197703 and JP-A-2010-96919, etc.
[0064] The weight average molecular weight (Mw) of the first methacrylic copolymer (A) is not particularly limited, and is preferably 40,000 to 400,000. The lower limit is more preferably 50,000, and particularly preferably 60,000. The upper limit is more preferably 300,000, and particularly preferably 200,000. When the first methacrylic copolymer (A) has an Mw of not less than the lower limit, it can have excellent mechanical properties, and when it has an Mw of not more than the upper limit, it can have excellent melt flowability and molding processability. In this specification, unless otherwise specified, the "weight average molecular weight (Mw)" is the weight average molecular weight calculated based on standard polymethyl methacrylate (PMMA) determined by gel permeation chromatography (GPC) analysis using a differential refractive index detector.
[0065] The glass transition temperature (Tg) of the first methacrylic copolymer (A) is 120°C or higher. The lower limit is preferably 123°C, more preferably 125°C, particularly preferably 130°C, and most preferably 135°C. The upper limit is not particularly limited, and is, for example, 150°C. The higher the Tg, the higher the heat resistance of the first methacrylic copolymer (A), which is preferable. A molded article containing the first methacrylic copolymer (A) having a high Tg is less likely to deform and / or shrink due to heat, which is preferable. In this specification, the "glass transition temperature (Tg)" can be measured in accordance with JIS K7121 by the method described in the section [Examples] below.
[0066] As described above, the thermoplastic resin composition of the present disclosure contains one or more organic disulfide compounds (D). The timing of adding the organic disulfide compound (D) is not particularly limited. The thermoplastic resin composition of the present disclosure can be preferably produced using an organic disulfide compound-added methacrylic copolymer (AD) containing a first methacrylic copolymer (A) and an organic disulfide compound (D).
[0067] The organic disulfide compound-added methacrylic copolymer (AD) can have excellent thermal decomposition resistance. For example, the thermal decomposition resistance can be measured by performing thermogravimetric analysis (TGA) under an inert gas atmosphere as an index of 1% thermal weight loss temperature. The organic disulfide compound-added methacrylic copolymer (AD) can have a 1% thermal weight loss temperature of, for example, 250°C or higher, 260°C or higher, 270°C or higher, or 280°C or higher. The upper limit of the 1% thermal weight loss temperature is not particularly limited, and can be, for example, 360°C or 350°C. The 1% thermal weight loss temperature can be measured using a thermogravimetric analyzer and is the temperature at which the weight loss rate is 1% relative to 100% weight before heating. For example, a TG curve can be obtained by performing thermogravimetric analysis (TGA) under conditions of heating from room temperature (20 to 25°C) to 500°C at a heating rate of 10°C / min in a nitrogen atmosphere, and the 1% thermal weight loss temperature can be obtained from this TG curve.
[0068] The organic disulfide compound-added methacrylic copolymer (AD) can have excellent heat resistance and rigidity even under load. The deflection temperature under load (HDT) of a test piece of the first methacrylic copolymer (A) having a length of 80 mm, a width of 10 mm and a thickness of 4 mm, measured in accordance with JIS K7191, can be, for example, 100°C or higher, 105°C or higher, or 110°C or higher. The upper limit is not particularly limited and is, for example, 150°C.
[0069] A test piece made of an organic disulfide compound-added methacrylic copolymer (AD) with a length of 80 mm, width of 10 mm, and thickness of 4 mm is cut with a notch of 0.25 mm tip radius and 2 mm depth, and the Charpy impact strength measured at room temperature (23±2°C) in accordance with JIS K7111 is, for example, 0.8 kJ / m 2 The lower limit is preferably 0.9 kJ / m 2 , more preferably 1 kJ / m 2 The upper limit is not particularly limited, and is, for example, 2 kJ / m 2 , or 1.5 kJ / m 2 It is.
[0070] (Graft Copolymer (B)) The content of the graft copolymer (B) in the thermoplastic resin composition of the present disclosure is 5 to 40% by mass. The lower limit is preferably 8% by mass, more preferably 10% by mass, and particularly preferably 15% by mass. The upper limit is preferably 35% by mass, more preferably 30% by mass, and particularly preferably 25% by mass. When the content of the graft copolymer (B) in the thermoplastic resin composition of the present disclosure is equal to or greater than the above lower limit, the thermoplastic resin composition can have excellent impact resistance, and when the content is equal to or less than the above upper limit, the thermoplastic resin composition can have excellent heat resistance and surface hardness.
[0071] The graft copolymer (B) is a copolymer obtained by graft copolymerizing a methacrylic copolymer (M) onto a butadiene-based rubbery polymer (BR) which contains butadiene units and may further contain one or more other units. The methacrylic copolymer (M) contains methyl methacrylate (MMA) units and one or more aromatic vinyl compound units. The methacrylic copolymer (M) may further contain one or more vinyl cyanide compound units, and may further contain one or more other units.
[0072] As described above, in the thermoplastic resin composition of the present disclosure containing an appropriate amount of organic disulfide compound (D), the gelation of the graft copolymer (B) containing butadiene units is effectively suppressed by the presence of an appropriate amount of organic disulfide compound (D) during the production of the resin composition and during heating and melting during molding, etc. As a result, a thermoplastic resin composition having excellent impact resistance at room temperature (21 to 25°C) and low temperature (e.g., below freezing point) can be stably produced. The butadiene unit content in the butadiene-based rubbery polymer (BR) is 60 to 100% by mass. The lower limit is preferably 65% by mass, more preferably 70% by mass. The present disclosure can effectively suppress gelation during heat melting even when a graft copolymer (B) having a high butadiene unit content is used.
[0073] The content of MMA units in the methacrylic copolymer (M) is 10 to 90% by mass. The lower limit is preferably 20% by mass, more preferably 30% by mass, particularly preferably 40% by mass, and most preferably 50% by mass. The upper limit is preferably 85% by mass, more preferably 80% by mass. The content of one or more aromatic vinyl compound units in the methacrylic copolymer (M) (the total amount when there are multiple types, unless otherwise specified) is 90 to 10% by mass. The lower limit is preferably 15% by mass, more preferably 20% by mass. The upper limit is preferably 80% by mass, more preferably 70% by mass, particularly preferably 60% by mass, and most preferably 50% by mass. The content of one or more vinyl cyanide compound units in the methacrylic copolymer (M) (the total amount when there are multiple types, unless otherwise specified) is 49 to 0 mass %. The upper limit is preferably 45 mass %, more preferably 40 mass %, particularly preferably 35 mass %, and most preferably 30 mass %. The content of one or more other monomer units in the methacrylic copolymer (M) (the total amount in the case of a plurality of types, unless otherwise specified) is not particularly limited and is preferably 0 to 5% by mass.
[0074] If the contents of MMA unit, aromatic vinyl compound unit, and vinyl cyanide compound unit in the methacrylic copolymer (M) are within the above ranges, the methacrylic copolymer (M) can have good heat resistance and polymerizability. It is relatively easy to control the copolymerization of the aromatic vinyl compound unit, and it is easy to obtain a methacrylic copolymer (M) having a uniform composition such as the content of the aromatic vinyl compound unit.
[0075] Examples of units other than butadiene units that can be contained in the butadiene-based rubbery polymer (BR) include conjugated diene compound units other than butadiene units, aromatic vinyl compound units, and vinyl cyanide compound units. Conjugated diene compounds other than butadiene are not particularly limited, and examples thereof include isoprene, 2,3-dimethyl-1,3-butadiene, 1,3-pentadiene, and 1,3-hexadiene. Preferred examples of the aromatic vinyl compound, the vinyl cyanide compound, and the other monomers are the same as those in the second methacrylic copolymer (C).
[0076] The butadiene-based rubbery polymer (BR) may be a hydrogenated product in which at least a portion of one or more conjugated diene compound units containing butadiene units has been hydrogenated (also called hydrogenation). The butadiene-based rubbery polymer (BR) may be one or more rubbery polymers selected from the group consisting of polybutadiene, a copolymer containing butadiene units and aromatic vinyl compound units (preferably styrene units), a copolymer containing butadiene units and vinyl cyanide compound units (preferably acrylonitrile units), and hydrogenated products thereof.
[0077] The content of the butadiene rubber-like polymer (BR) in the graft copolymer (B) is not particularly limited, and is preferably 40 to 80% by mass, and the upper limit is more preferably 55% by mass. The content of the methacrylic copolymer (M) in the graft copolymer (B) is not particularly limited, and is preferably 60 to 20% by mass, and the lower limit is more preferably 45% by mass. When the content of the butadiene-based rubbery polymer (BR) in the graft copolymer (B) is equal to or more than the above lower limit, the graft copolymer (B) and the thermoplastic resin composition of the present disclosure can have excellent impact resistance. When the content of the methacrylic copolymer (M) in the graft copolymer (B) is equal to or more than the above lower limit, the graft copolymer (B) and the thermoplastic resin composition of the present disclosure can have excellent heat resistance and molding processability.
[0078] The form of the graft copolymer (B) is not particularly limited, and is preferably a core-shell type graft copolymer particle in which at least a part of the surface of a core particle made of a butadiene-based rubber-like polymer (BR) is covered with a shell layer made of a methacrylic copolymer (M). The shell layer made of the methacrylic copolymer (M) is also called a graft layer.
[0079] The volume average particle size (d50) of the graft copolymer (B) is not particularly limited, and is preferably 0.20 to 0.60 μm. The lower limit is more preferably 0.25 μm, particularly preferably 0.30 μm, and most preferably 0.35 μm. The upper limit is more preferably 0.50 μm, and particularly preferably 0.40 μm. When the volume average particle diameter (d50) is equal to or greater than the lower limit, the graft copolymer (B) and the thermoplastic resin composition of the present disclosure can have excellent impact resistance. When the volume average particle diameter (d50) is equal to or less than the upper limit, the thermoplastic resin composition of the present disclosure can have excellent transparency and moldability.
[0080] The volume average particle diameter (d50) of the graft copolymer (B) can be adjusted by the volume average particle diameter (d50) of the core particles made of the butadiene-based rubber-like polymer (BR) and the polymerization conditions such as the mass ratio of the butadiene-based rubber-like polymer (BR) to the methacrylic copolymer (M). In this specification, unless otherwise specified, the "volume average particle size (d50)" is the volume-based median size measured using a light scattering particle size distribution measuring device.
[0081] The graft copolymer (B) can be produced by a known method. The method for producing the graft copolymer (B) includes the steps of: A step (SB-1) of preparing core particles made of a butadiene-based rubber-like polymer (BR) and a plurality of raw material monomers of a methacrylic copolymer (M) (specifically, a plurality of monomers including methyl methacrylate (MMA) and one or more aromatic vinyl compound units); The method may further comprise a step (SB-2) of copolymerizing a plurality of raw material monomers for the methacrylic copolymer (M) in the presence of the core particles.
[0082] Examples of the copolymerization method in step (SB-2) include bulk polymerization, solution polymerization, suspension polymerization, bulk-suspension polymerization, and emulsion polymerization, and emulsion polymerization is preferred. In step (SB-2), a polymerization initiator and, if necessary, a chain transfer agent can be used. Examples of the polymerization initiator and the chain transfer agent are the same as those in step (S1-1) described below. The amount of the polymerization initiator used is not particularly limited, and is preferably 0.1 to 0.5 parts by mass, more preferably 0.5 to 3.5 parts by mass, relative to 100 parts by mass of the total amount of the raw material monomers. The polymerization temperature is not particularly limited, and is preferably 50 to 98°C. The lower limit is more preferably 55°C, and the upper limit is more preferably 90°C.
[0083] In the step (SB-2), a methacrylic copolymer that is not bonded to the butadiene rubber-like polymer (BR) may be produced as a by-product. Therefore, the graft copolymer (B) may contain a small amount (for example, about 0 to 15 mass%) of a by-product methacrylic copolymer that is not bonded to the butadiene rubber-like polymer (BR). The unit composition of the methacrylic copolymer (M) constituting the graft chain of the graft copolymer (B) is usually the same as the unit composition of the by-product methacrylic copolymer that is not bonded to the butadiene rubber-like polymer (BR).
[0084] (Second Methacrylic Copolymer (C)) The content of the second methacrylic copolymer (C) in the thermoplastic resin composition of the present disclosure is 0 to 85% by mass. The lower limit is preferably 5% by mass, more preferably 10% by mass. The upper limit is preferably 70% by mass, more preferably 60% by mass. The thermoplastic resin composition of the present disclosure containing an appropriate amount of the second methacrylic copolymer (C) can have excellent moldability.
[0085] The second methacrylic copolymer (C) contains methyl methacrylate (MMA) units and one or more aromatic vinyl compound units other than isopropenyl aromatic compound units. The second methacrylic copolymer (C) may further contain one or more vinyl cyanide compound units, and may further contain one or more other units. The second methacrylic copolymer (C) may not contain isopropenyl aromatic compound units.
[0086] The content of MMA units in the second methacrylic copolymer (C) is 10 to 90% by mass. The lower limit is preferably 20% by mass, more preferably 30% by mass, particularly preferably 40% by mass, and most preferably 50% by mass. The upper limit is preferably 85% by mass, more preferably 80% by mass, and particularly preferably 75% by mass. The content of one or more aromatic vinyl compound units in the second methacrylic copolymer (C) (the total amount when there are multiple types, unless otherwise specified) is 70 to 10 mass%. The lower limit is preferably 5 mass%, more preferably 10 mass%, even more preferably 12 mass%, particularly preferably 15 mass%, and most preferably 20 mass%. The upper limit is preferably 60 mass%, more preferably 50 mass%, even more preferably 40 mass%, particularly preferably 30 mass%, and most preferably 25 mass%. The content of one or more vinyl cyanide compound units in the second methacrylic copolymer (C) (the total amount when there are multiple types, unless otherwise specified) is 49 to 0 mass%, and the upper limit is preferably 45 mass%, more preferably 40 mass%, particularly preferably 35 mass%, and most preferably 30 mass%. The content of one or more other monomer units in the second methacrylic copolymer (C) (the total amount in the case of a plurality of types, unless otherwise specified) is not particularly limited and is preferably 0 to 5 mass %.
[0087] If the content of MMA unit, aromatic vinyl compound unit, and vinyl cyanide compound unit are within the above ranges, the second methacrylic copolymer (C) can have good transparency, heat resistance, polymerizability, and moldability. If the content of MMA unit and the content of aromatic vinyl compound unit are within the above ranges, the second methacrylic copolymer (C) can be relatively easy to control the copolymerization of aromatic vinyl compound unit, and the second methacrylic copolymer (C) having a uniform composition such as the content of aromatic vinyl compound unit can be stably produced, and the second methacrylic copolymer (C) having good heat resistance and mechanical properties such as rigidity and surface hardness can be stably produced.
[0088] The second methacrylic copolymer (C) is obtained by copolymerizing methyl methacrylate (MMA), one or more aromatic vinyl compounds, optionally one or more vinyl cyanide compounds, and optionally one or more other monomers. The aromatic vinyl compound other than the isopropenyl aromatic compound is not particularly limited, and examples thereof include styrene (St); alkyl-substituted styrenes such as o-, m-, or p-methylstyrene, 2,4-dimethylstyrene, 2,5-dimethylstyrene, 3,4-dimethylstyrene, 3,5-dimethylstyrene, o-, m-, or p-ethylstyrene; and 1,1-diphenylethylene. From the viewpoints of the melt flowability and productivity of the second methacrylic copolymer (C), styrene (St) is preferred.
[0089] The vinyl cyanide compound is not particularly limited, and examples thereof include acrylonitrile (AN), methacrylonitrile, fumaronitrile, vinylidene cyanide, etc. From the viewpoints of availability and refractive index adjustment, acrylonitrile (AN) etc. is preferred. Examples of the other monomer include vinyl monomers having one polymerizable unsaturated bond in one molecule other than methyl methacrylate (MMA) and aromatic vinyl compounds, such as (meth)acrylic acid, (meth)acrylic acid esters other than MMA, and (meth)acrylamide.
[0090] The weight average molecular weight (Mw) of the second methacrylic copolymer (C) is not particularly limited, and is preferably 40,000 to 400,000. The lower limit is more preferably 50,000, and particularly preferably 60,000. The upper limit is more preferably 300,000, and particularly preferably 200,000. If the second methacrylic copolymer (C) has an Mw of not less than the lower limit, it can have excellent mechanical properties, and if it has an Mw of not more than the upper limit, it can have excellent melt flowability and molding processability.
[0091] The glass transition temperature (Tg) of the second methacrylic copolymer (C) is not particularly limited, and from the viewpoint of heat resistance, it is preferably 95° C. or higher. The lower limit is more preferably 98° C., and particularly preferably 100° C. From the viewpoint of the moldability of the thermoplastic resin composition of the present disclosure, the Tg of the second methacrylic copolymer (C) is preferably lower than the Tg of the first methacrylic copolymer (A). The upper limit of the Tg of the second methacrylic copolymer (C) is preferably 125°C, more preferably 120°C, even more preferably 115°C, even more preferably 110°C, particularly preferably 107°C, and most preferably 105°C.
[0092] (Other polymers) The thermoplastic resin composition of the present disclosure may contain one or more other polymers to the extent that the effects of the present disclosure are not impaired. Examples of the other polymers include methacrylic resins other than the above-mentioned methacrylic copolymers (A) and (C); polyolefin resins such as polyethylene, polypropylene, polybutene-1, poly-4-methylpentene-1, and polynorbornene; styrene resins other than those mentioned above, such as polystyrene, styrene-maleic anhydride copolymer (SMA resin), acrylonitrile-styrene copolymer (AS resin), acrylonitrile-butadiene-styrene (ABS) resin, acrylonitrile-ethylene-propylene-diene-styrene (AES) resin, acrylic-acrylonitrile-styrene (AAS) resin, acrylonitrile-chlorinated ethylene-styrene (ACS) resin, methacrylic butadiene styrene (MBS) resin, and silicon-acrylonitrile-styrene (SAS) resin; polyester resins such as polyethylene terephthalate and polybutylene terephthalate; and polyamide elastomers such as nylon 6, nylon 66, and polyamide elastomers. Examples of the thermoplastic resin include amide-based resins; polyimides, polyetherimides; polycarbonate-based resins; other thermoplastic resins such as polyvinyl chloride, polyvinylidene chloride, polyvinylidene fluoride, polyvinyl alcohol, ethylene-vinyl alcohol copolymers, polyacetals, ethylene-vinyl acetate copolymers, phenoxy-based resins, polysulfones, polyphenylene sulfides, polyether ether ketones, polyphenylene oxides, modified polyphenylene ethers, and ethylene-based ionomers; thermosetting resins such as phenol-based resins, melamine-based resins, silicone-based resins, and epoxy-based resins; polyurethanes and chlorinated polyurethane resins; silicone-modified resins; acrylic rubbers, silicone rubbers; acrylic thermoplastic elastomers such as acrylic multilayered polymer particles and acrylic block copolymers; styrene-based thermoplastic elastomers such as SEPS, SEBS, and SIS; and olefin-based rubbers such as IR, EPR, and EPDM.
[0093] The total content of the first methacrylic copolymer (A), the graft copolymer (B), and the second methacrylic copolymer (C) in the thermoplastic resin composition of the present disclosure is preferably 90 to 100% by mass, and the lower limit is more preferably 95% by mass. The amount of other polymers in the thermoplastic resin composition of the present disclosure (the total amount when multiple types are used, unless otherwise specified) is preferably 10 to 0 mass %, and the upper limit is more preferably 5 mass %.
[0094] (Filler) The thermoplastic resin composition of the present disclosure may contain one or more fillers as additives, if necessary, within the scope of not impairing the effects of the present disclosure. Examples of the filler include inorganic fine particles including metal oxides such as silicon oxide (silica) and titanium oxide, metal carbonates such as calcium carbonate and magnesium carbonate, metal sulfates such as barium sulfate, carbon black, talc, clay, or combinations thereof; organic fine particles such as polysiloxane-based crosslinked polymer fine particles; and combinations thereof. The filler can function as a light diffusing agent or a matting agent. From the viewpoint of transparency, the content of the filler in the thermoplastic resin composition of the present disclosure is preferably small, and is preferably 0 to 3 mass%. The upper limit is more preferably 1.5 mass%, particularly preferably 1 mass%, and most preferably 0.5 mass%. The thermoplastic resin composition of the present disclosure preferably does not contain any particles other than the core-shell type graft copolymer particles made of the graft copolymer (B).
[0095] (Additives other than those mentioned above) The thermoplastic resin composition of the present disclosure may contain, as an additive, one or more other additives other than the organic disulfide compound (D) and the filler, as long as the effects of the present invention are not impaired. Other additives include antioxidants, heat deterioration inhibitors, UV absorbers, light stabilizers, lubricants, release agents, polymer processing aids, antistatic agents, flame retardants, colorants (dyes, pigments, organic dyes, etc.), and fluorescent materials. The content of the organic disulfide compound (D) and the other additives other than the filler in the thermoplastic resin composition of the present disclosure (the total amount in the case of a plurality of kinds, unless otherwise specified) is preferably 0 to 7 mass % from the viewpoint of suppressing defective appearance of the molded article. The upper limit is more preferably 5 mass %, particularly preferably 4 mass %.
[0096] The timing of addition of other polymers and additives other than the organic disulfide compound (D) that may be contained in the thermoplastic resin composition of the present disclosure is not particularly limited, and is optional, similar to the timing of addition of the organic disulfide compound (D).
[0097] [Method of producing thermoplastic resin composition] The method for producing the thermoplastic resin composition of the present disclosure is not particularly limited.The method for producing the thermoplastic resin composition of the present disclosure can have, for example, a step of melt-kneading one or more first methacrylic copolymers (A), one or more graft copolymers (B), if necessary one or more second methacrylic copolymers (C), and if necessary one or more other polymers. In the method for producing a thermoplastic resin composition of the present disclosure, one or more additives including an organic disulfide compound (D) can be added at any timing.
[0098] A method for producing a thermoplastic resin composition according to one embodiment of the present invention includes the steps of: A step (S1) of producing an organic disulfide compound-added methacrylic copolymer (AD) containing a first methacrylic copolymer (A) and an organic disulfide compound (D); The method includes a step (S2) of melt-kneading 10 to 95% by mass of an organic disulfide compound-added methacrylic copolymer (AD), 5 to 40% by mass of a graft copolymer (B), and 0 to 85% by mass of a second methacrylic copolymer (C).
[0099] (Process (S1)) Step (S1) A step (S1-1) of preparing a polymerization raw material containing methyl methacrylate (MMA) and one or more isopropenyl aromatic compounds (I) as raw material monomers and further containing a polymerization initiator; A step (S1-2) of polymerizing the polymerization raw material to obtain a resin solution containing a first methacrylic copolymer (A) or a precursor resin thereof; The method may include a step (S1-3) of volatilizing and removing at least a portion of the raw material monomers present in the resin solution in one or more steps to obtain a first methacrylic copolymer (A) or a precursor resin thereof. When step (S1-3) is a step of obtaining a precursor resin of the first methacrylic copolymer (A), step (S1) can further include a step (S1-4) of obtaining the first methacrylic copolymer (A) from the precursor resin by glutarimide cyclization reaction or the like. In the method for producing a thermoplastic resin composition of the present embodiment, one or more organic disulfide compounds (D) can be added to at least one of the polymerization raw materials, the resin solution obtained after completion of step (S1-2), and the resin solution during the course of step (S1-3).
[0100] <Process (S1-1)> A polymerization raw material containing the above-mentioned multiple raw material monomers and a polymerization initiator is prepared. As the polymerization initiator, one or more known radical polymerization initiators can be used. Specific examples include t-hexylperoxyisopropyl monocarbonate, t-hexylperoxy 2-ethylhexanoate, 1,1,3,3-tetramethylbutylperoxy 2-ethylhexanoate, t-butylperoxypivalate, t-hexylperoxypivalate, t-butylperoxyneodecanoate, t-hexylperoxyneodecanoate, 1,1,3,3-tetramethylbutylperoxyneodecanoate, 1,1-bis(t-hexylperoxy)cyclohexane, benzoyl peroxide, 3,5,5-trimethylhexanoyl peroxide, lauroyl peroxide, 2,2'-azobis(2-methylpropionitrile) (AIBN), 2,2'-azobis(2-methylbutyronitrile), and dimethyl 2,2'-azobis(2-methylpropionate). Among these, 2,2'-azobis(2-methylpropionitrile) (AIBN), t-hexylperoxy 2-ethylhexanoate, 1,1-bis(t-hexylperoxy)cyclohexane, and dimethyl 2,2'-azobis(2-methylpropionate) are preferred.
[0101] The polymerization raw material may contain one or more chain transfer agents as necessary. The chain transfer agent can be used for the purpose of adjusting the molecular weight of the first methacrylic copolymer (A). Examples of the chain transfer agent include alkyl mercaptans such as n-octyl mercaptan (n-OM), n-dodecyl mercaptan, t-dodecyl mercaptan, 1,4-butanedithiol, 1,6-hexanedithiol, ethylene glycol bisthiopropionate, butanediol bisthioglycolate, butanediol bisthiopropionate, hexanediol bisthioglycolate, hexanediol bisthiopropionate, trimethylolpropane tris-(β-thiopropionate), and pentaerythritol tetrakisthiopropionate; α-methylstyrene (αMSt) dimer; and terpinolene. Among these, monofunctional alkyl mercaptans such as n-octyl mercaptan (n-OM) and n-dodecyl mercaptan are preferred. The amount of chain transfer agent used (total amount when multiple types are used, unless otherwise specified) is not particularly limited, and is preferably 0 to 1 part by mass relative to 100 parts by mass of the total amount of multiple types of raw material monomers. The upper limit is more preferably 0.5 parts by mass, particularly preferably 0.4 parts by mass, and most preferably 0.3 parts by mass.
[0102] The polymerization raw material may contain one or more additives other than those mentioned above, if necessary. The polymerization raw materials can be prepared by mixing multiple raw material monomers, one or more polymerization initiators, one or more chain transfer agents as required, and one or more additives as required under an inert gas atmosphere such as nitrogen gas or in the presence of oxygen. They may be mixed all at once or in portions, and the blending procedure in the case of portion mixing is not particularly limited. The content of water in the polymerization raw material is preferably 0 to 1000 ppm. The upper limit is more preferably 700 ppm, particularly preferably 280 ppm. The polymerization raw material can be dehydrated by a known method, if necessary. The polymerization raw material is preferably adjusted to have a dissolved oxygen content of 0 to 10 ppm by nitrogen purging, etc. The upper limit of the dissolved oxygen content is more preferably 5 ppm, particularly preferably 4 ppm, and most preferably 3 ppm.
[0103] <Process (S1-2)> The polymerization can be carried out by a known method, and the bulk polymerization method is preferred. For example, the polymerization raw material prepared in step (S1-1) is continuously fed into a tank reactor, bulk polymerization is carried out in the tank reactor, a resin solution containing the first methacrylic copolymer (A) or its precursor resin is obtained, and the obtained resin solution is continuously extracted from the tank reactor, which is a continuous bulk polymerization method. The polymerization is preferably carried out under an atmosphere of an inert gas such as nitrogen gas. The polymerization temperature is not particularly limited, and is preferably 110 to 160°C, and more preferably 120 to 155°C. The average residence time in the tank reactor is not particularly limited, and is preferably 1.5 to 6 hours, more preferably 2 to 5.5 hours, and particularly preferably 2.5 to 5 hours. The average concentration of the radical polymerization initiator in the liquid in the tank reactor is not particularly limited, and is preferably 1.0×10 -6 ~2.0×10 -5 It is in mol / L. The polymerization conversion rate is preferably 20 to 60%. The lower limit is more preferably 25%. The upper limit is preferably 55%, more preferably 50%.
[0104] <Process (S1-3)> At least a portion of the unreacted raw material monomers present in the resin solution is removed by volatilization in one or more stages. Examples of the volatilization method include an adiabatic flash evaporation method, an equilibrium flash evaporation method, and a combination thereof, and an adiabatic flash evaporation method is preferred. The unreacted raw material monomers present in the resin solution can be removed by volatilization in a known manner using a heat exchanger, a vented extruder, or a combination of these, and the combined use of a heat exchanger and a vented extruder is preferred.
[0105] The heating temperature by the heat exchanger (also referred to as the set temperature of the heat exchanger or the heat exchanger temperature) is not particularly limited, and is preferably 180 to 280° C. The lower limit is more preferably 190° C., and particularly preferably 200° C. The upper limit is more preferably 270° C., particularly preferably 260° C., and most preferably 250° C. Examples of the extruder include a single-screw extruder, a twin-screw extruder, and a multi-screw extruder. The extruder has a resin inlet into which the resin solution is introduced, a cylinder with a built-in screw, and a die including a resin outlet for discharging the first methacrylic copolymer (A) obtained after the step (S1-3), and may have an additive supply port as necessary. The number of vents contained in the vented extruder is one or more, and preferably multiple. The molten resin temperature in the die (also referred to as the die resin temperature) is not particularly limited, and is preferably 230 to 260°C. The lower limit is more preferably 235°C, and particularly preferably 240°C. The upper limit is more preferably 255°C, and particularly preferably 250°C.
[0106] When the heating temperature by the heat exchanger and the molten resin temperature in the die are within the above ranges, the thermal decomposition of the first methacrylic copolymer (A) is suppressed, and a first methacrylic copolymer (A) having excellent heat resistance and thermal decomposition resistance (thermal stability) can be produced. In addition, a first methacrylic copolymer (A) having a uniform composition, such as the content of isopropenyl aromatic compound units (UI), can be stably produced, and a first methacrylic copolymer (A) having good heat resistance and mechanical properties, such as rigidity and surface hardness, can be stably produced. The unreacted raw material monomer removed from the resin solution may be recovered and reused as the raw material monomer.
[0107] In the production method of this embodiment, one or more organic disulfide compounds (D) can be added to at least one of the polymerization raw materials, the resin solution obtained after completion of step (S1-2), and the resin solution during step (S1-3) so that an appropriate amount of one or more organic disulfide compounds (D) is present in the organic disulfide compound-added methacrylic copolymer (AD) obtained after step (S1). Of the polymerization raw materials, the resin solution obtained after the end of step (S1-2), and the resin solution during step (S1-3), it is preferable to add one or more organic disulfide compounds (D) at least to the polymerization raw materials.
[0108] The amount of organic disulfide compound (D) added to the polymerization raw material (total amount when multiple types are used unless otherwise specified) is preferably 10 to 2000 ppm. The lower limit is more preferably 20 ppm, even more preferably 30 ppm, even more preferably 50 ppm, even more preferably 80 ppm, particularly preferably 100 ppm, and most preferably 200 ppm. The upper limit is more preferably 1500 ppm, particularly preferably 1200 ppm, and most preferably 1000 ppm.
[0109] The content of the organic disulfide compound (D) in the organic disulfide compound-added methacrylic copolymer (AD) obtained after step (S1) (unless otherwise specified, the total amount in the case of a plurality of types) is preferably 10 to 2000 ppm. The lower limit is more preferably 20 ppm, even more preferably 30 ppm, even more preferably 50 ppm, even more preferably 80 ppm, particularly preferably 100 ppm, and most preferably 150 ppm. The upper limit is more preferably 1500 ppm, particularly preferably 1200 ppm, and most preferably 1000 ppm. The organic disulfide compound-added methacrylic copolymer (AD) contains a first methacrylic copolymer (A) containing an isopropenyl aromatic compound unit (UI) and an appropriate amount of an organic disulfide compound (D), and can have excellent heat resistance, thermal decomposition resistance (thermal stability), surface hardness, and impact resistance.
[0110] In general, methacrylic copolymers containing MMA units and isopropenyl aromatic compound units such as αMSt units tend to have a relatively low thermal decomposition temperature. Therefore, when the copolymer is heated and melted during resin production and molding, the copolymer is thermally decomposed, the amount of residual monomers in the resin increases, and the heat resistance may decrease. In addition, when the resin is produced and molded, if the residence time in a heated and melted state is long, the thermal decomposition of the methacrylic copolymer may cause poor appearance such as foaming.
[0111] In the production method of this embodiment, in step (S1), the presence of an appropriate amount of the organic disulfide compound (D) effectively suppresses the thermal decomposition of the first methacrylic copolymer (A). As a result, the first methacrylic copolymer (A) having a small amount of residual monomer and excellent heat resistance and thermal decomposition resistance (thermal stability) can be stably produced. Furthermore, in step (S1), the presence of an appropriate amount of the organic disulfide compound (D) makes it relatively easy to control the copolymerization of the isopropenyl aromatic compound (I), and enables the stable production of a first methacrylic copolymer (A) having a uniform composition, such as the content of isopropenyl aromatic compound units (UI), and thus enables the stable production of a first methacrylic copolymer (A) having good heat resistance and mechanical properties, such as rigidity and surface hardness. In the step (S1), even if the residence time in a heated and molten state is long, defects in appearance such as foaming caused by thermal decomposition of the first methacrylic copolymer (A) are suppressed.
[0112] The organic disulfide compound-added methacrylic copolymer (AD) can effectively suppress thermal decomposition of the first methacrylic copolymer (A) and the second methacrylic copolymer (C) which may be contained as an optional component, and gelation of the graft copolymer (B) due to the presence of an appropriate amount of the organic disulfide compound (D), even during heating and melting in step (S2) and subsequent molding processing.
[0113] (Process (S2)) The melt-kneading can be carried out in one stage or multiple stages, and the procedure for blending multiple types of copolymers is optional. The melt-kneading can be carried out using a known mixing or kneading device such as an extruder (preferably a twin-screw extruder), a kneader-ruder, a mixing roll, or a Banbury mixer. The thermoplastic resin composition of the present disclosure can be processed by known methods into a form suitable for use as a molding material, such as pellets or powder.
[0114] As described above, according to the present disclosure, it is possible to provide a thermoplastic resin composition that contains a graft copolymer containing a butadiene unit and a methacrylic copolymer, and has good transparency, heat resistance, surface hardness, and impact resistance at room temperature and low temperature, and a production method thereof.
[0115] [Molded body] The molded article of the present disclosure includes a layer or member made of the thermoplastic resin composition of the present disclosure, and may be a layer or member entirely made of the thermoplastic resin composition of the present disclosure. The form of the molded article is not particularly limited, and examples thereof include planar objects having a single-layer structure or a laminate structure such as films, sheets, and plates; fibers, pipes, tubes, rods; particles; and any three-dimensional structures. The molded article may be a laminate or a composite including a layer or member made of the thermoplastic resin composition of the present disclosure and a layer or member made of other resins or various materials other than resins. The molded article obtained by the known molding method may be subjected to surface treatments such as printing, painting, plating, vapor deposition, and sputtering; and shape processing such as curving, bending, and cutting (also called secondary molding), as necessary. Generally, the terms "film," "sheet," and "plate" are used for thin film molded bodies depending on their thickness, but there is no clear definition for these terms and no clear distinction between them.
[0116] The molding method is not particularly limited, and examples thereof include melt molding methods such as extrusion molding, injection molding, inflation molding, blow molding, and calendar molding; compression molding (also called press molding); vacuum molding and pressure molding; and solution casting (also called solution casting). Among the above, the melt molding method is preferred. The melt molding temperature is not particularly limited, and is preferably 180 to 280° C., more preferably 200 to 260° C. The thermoplastic resin composition of the present disclosure containing one or more organic disulfide compounds (D) has excellent thermal decomposition resistance (thermal stability), and therefore, even when heated at a relatively high temperature, thermal decomposition and gelation are suppressed, and a high-quality molded product with good appearance can be provided.
[0117] [Application] The thermoplastic resin composition of the present disclosure and a molded article containing the same can be used for any application. Applications include furniture, household goods, storage and stockpiling items, building materials such as walls and roofs, toys and play equipment, gaming applications such as pachinko face plates, medical and welfare products, office automation equipment, audiovisual equipment, batteries and electrical equipment, lighting equipment, and vehicle applications. The thermoplastic resin composition of the present disclosure and a molded article containing the same are suitable for optical applications; mobile applications such as main body parts and interior and exterior components for automobiles, ships, and aircraft; decorative applications; and electrical and electronic applications.
[0118] Examples of optical applications include display applications such as liquid crystal displays, plasma displays, organic electroluminescence (EL) displays, and touch panel displays combining a touch panel with various displays. Examples of optical components for displays include display substrates, display front panels, polarizer protective films, retardation plates, optical compensation films (viewing angle control films, etc.), transparent conductive substrates for touch panels, light guide plates, and lenses (arrays). In this specification, unless otherwise specified, "lens (array)" is a general term for lenses and lens arrays. Other optical components include optical components for solar cells (transparent substrates, back films, front films, etc.); optical components used in fields such as optical communications, optical switching, and optical measurement (waveguides, lenses (arrays), optical fibers, and optical fiber coating materials, etc.); and optical components for light-emitting elements such as light-emitting diodes (LEDs) (lenses, lens covers, etc.).
[0119] Mobile body applications include automobile interior parts such as side visors, rear visors, head wings, headlight covers, instrument panel parts, air conditioner outlets, dashboards, and console boxes; and automobile exterior parts such as mirror housings, spoilers, pillar garnishes, wheel caps, rear lamp housings, bumpers, front grilles, rear grilles, and license plate garnishes.
[0120] Examples of decorative applications include decorative films including a substrate film and a decorative layer, decorative members (e.g., decorative panels) in which a decorative film is laminated on at least a portion of the surface of a substrate (also called a support member), and decorative molded bodies in which a decorative film is laminated on at least a portion of the surface of an adherend, etc. Examples of decorative layers include metal layers, colored layers, printed layers, nonwoven fabrics, artificial leathers, natural leathers, and combinations thereof. The thermoplastic resin composition of the present disclosure is suitable for use as a base film for a decorative film, a base material (support member) for a decorative member, and the like. The thickness of the base material (support member) for the decorative member can be appropriately designed within a range that can adequately support the decorative film, and is, for example, 0.01 to 4.0 mm. The lower limit is preferably 0.05 mm, more preferably 0.1 mm. The upper limit is preferably 3.0 mm, more preferably 2.0 mm, and particularly preferably 1.0 mm.
[0121] In recent years, for applications such as automobile interior components, decorative films (also called optical decorative films) that can display information by transmitting light projected from one side to the other side; decorative panels in which an optical decorative film is laminated on a substrate (support member); and display devices equipped with such decorative panels have been developed. Conventionally, methyl methacrylate-butadiene-styrene resin (MBS resin) and acrylonitrile-butadiene-styrene resin (ABS resin) have been generally used for this purpose. However, these resins do not have high heat resistance and cannot withstand the heat during film insert molding, which may cause appearance defects. The thermoplastic resin composition of the present disclosure has excellent transparency, heat resistance, impact resistance, and moldability, and is stable against heat during film insert molding, etc., and is suitable for transparent substrate films for optically decorated films and transparent substrates (transparent support members) for decorative panels, etc.
[0122] Electrical and electronic applications include electronic devices with displays, such as personal computers, televisions, car navigation systems, mobile phones, tablet devices, electronic paper, electronic dictionaries, electronic organizers, electronic desk calculators, and game consoles; office equipment, such as recording medium drives and readers, keyboards, numeric keypads, mice, printers, copiers, scanners, and fax machines; cameras and video cameras; audio players, such as CD players and MD players, and portable radios; battery packs; and home appliances, such as hair dryers, electric kettles, and lighting equipment. EXAMPLES
[0123] Examples and comparative examples according to the present invention will be described. [Evaluation items and evaluation methods] The evaluation items and evaluation methods are as follows. (Polymerization conversion rate) The polymerization conversion rate was determined by gas chromatography analysis. A column, INERTCAP1 (film thickness 0.4 μm, inner diameter 0.25 mmφ, length 60 m), manufactured by GL Sciences Inc., was connected to a gas chromatograph GC-14A manufactured by Shimadzu Corporation. The analysis was carried out under the following conditions, and the polymerization conversion rate was calculated from the obtained data. Injection temperature: 250℃, Detector temperature: 250℃, Temperature profile: Hold at 60°C for 5 minutes → Heat to 250°C at a rate of 10°C / min → Hold at 250°C for 10 minutes.
[0124] (Weight average molecular weight (Mw)) The weight average molecular weight (Mw) of the resin was determined by gel permeation chromatography (GPC). The measurement device used was a GPC device "HLC-8320" manufactured by Tosoh Corporation. The separation column used was a series connection of "TSKguardcolumSuperHZ-H", "TSKgelHZM-M" and "TSKgelSuperHZ4000" manufactured by Tosoh Corporation. The detector used was a differential refractive index detector (RI detector). A sample solution was prepared by dissolving 4 mg of the resin to be measured in 5 ml of tetrahydrofuran. The temperature of the column oven was set to 40°C. Tetrahydrofuran was used as the eluent, the eluent flow rate was set to 0.35 ml / min, and 20 μl of the sample solution was injected into the device to measure the chromatogram. GPC measurements were performed on 10 standard polymethyl methacrylate (PMMA) points with molecular weights in the range of 400 to 5,000,000, and a calibration curve showing the relationship between retention time and molecular weight was created. Based on this calibration curve, the Mw of the resin to be measured in terms of standard PMMA was determined.
[0125] (Glass transition temperature (Tg)) The glass transition temperature (Tg) of the resin to be measured was measured using a differential scanning calorimeter (Shimadzu Corporation's "DSC-50") in accordance with JIS K7121. 10 mg of the resin to be measured was placed in an aluminum pan and set in the above-mentioned device. After nitrogen replacement for 30 minutes or more, the temperature was raised from room temperature (20 to 25°C) to 250°C at a rate of 20°C / min in a nitrogen flow of 10 ml / min, held for 5 minutes, and cooled to room temperature (first scan). Next, the temperature was raised to 200°C at a rate of 10°C / min (second scan), and a DSC curve was measured. The midpoint glass transition temperature obtained from the DSC curve obtained by the second scan was taken as the glass transition temperature (Tg).
[0126] (Unit composition of methacrylic copolymer) 1 H-NMR spectrum or 13 The C-NMR spectrum was measured, and the unit composition of the methacrylic copolymer was determined from the ratio of the integral values of the peaks derived from each unit. An example of a specific measurement method is shown below.
[0127] Regarding methyl methacrylate-α-methylstyrene copolymer (MMA-αMSt copolymer), 1 The H-NMR spectrum was measured to identify the peaks derived from the protons of the methoxy group of the methyl methacrylate (MMA) unit and the peaks derived from the protons of the phenyl group of the α-methylstyrene (αMSt) unit, and the unit composition was calculated from the ratio of the integral values of each peak.
[0128] For methyl methacrylate-α-methylstyrene-styrene copolymer (MMA-αMSt-St copolymer), measurement mode: reverse gated decoupling method, 13 The C-NMR spectrum was measured to identify the peaks derived from the carbon of the carbonyl group of the methyl methacrylate (MMA) unit, the peaks derived from the carbon of the phenyl group of the α-methylstyrene (αMSt) unit, and the peaks derived from the carbon of the phenyl group of the styrene (St) unit, and the unit composition was calculated from the ratio of the integral values of each peak.
[0129] For methyl methacrylate-α-methylstyrene-maleic anhydride copolymer (MMA-αMSt-Mah copolymer), the measurement mode was set to the reverse gated decoupling method. 13 The C-NMR spectrum was measured to identify the peaks derived from the carbon of the carbonyl group of the methyl methacrylate (MMA) unit, the peaks derived from the carbon of the phenyl group of the α-methylstyrene (αMSt) unit, and the peaks derived from the carbon of the carbonyl group of the maleic anhydride (Mah) unit, and the unit composition was calculated from the ratio of the integral values of each peak.
[0130] For methyl methacrylate-α-methylstyrene-cyclohexylmaleimide copolymer (MMA-αMSt-ChMI copolymer), measurement mode: reverse gated decoupling method, 13 The C-NMR spectrum was measured to identify the peaks derived from the carbon of the carbonyl group of the methyl methacrylate (MMA) unit, the peaks derived from the carbon of the phenyl group of the α-methylstyrene (αMSt) unit, and the peaks derived from the carbon of the carbonyl group of the cyclohexylmaleimide unit, and the unit composition was calculated from the ratio of the integral values of each peak.
[0131] For methyl methacrylate-styrene-cyclohexylmaleimide-phenylmaleimide copolymer (MMA-St-ChMI-PhMI copolymer), measurement mode: reverse gated decoupling method, 13 The C-NMR spectrum was measured to identify the peaks derived from the carbon of the carbonyl group of the methyl methacrylate (MMA) unit, the peaks derived from the carbon of the phenyl group of the styrene (St) unit, the peaks derived from the carbon of the carbonyl group of the cyclohexylmaleimide unit, and the peaks derived from the carbon of the carbonyl group of the phenylmaleimide unit, and the unit composition was calculated from the ratio of the integral values of each peak.
[0132] Regarding methyl methacrylate-α-methylstyrene-styrene-methyl glutarimide copolymer (MMA-αMSt-St-MeGI copolymer), 1The H-NMR spectrum was measured, and a peak due to the protons of methyl methacrylate (MMA) and a peak due to the protons of the glutarimide unit were identified. The integral values of the above two peaks were determined, and the glutarimide cyclization rate (mol %) was calculated based on the following formula. [Glutarimide cyclization rate](mol%)=[S G / (S M +S G )] x 100 In the above formula, S M is the integral value of the peak derived from the MMA unit, and S G is the integral value of the peak derived from the glutarimide unit. The glutarimide cyclization rate (mol %) was converted to the glutarimide cyclization rate (mass %) using the molecular weight of each unit. The unit composition of the methyl methacrylate-α-methylstyrene-styrene-methylglutarimide copolymer (MMA-αMSt-St-MeGI copolymer) was calculated from the unit composition of the methyl methacrylate-α-methylstyrene-styrene copolymer (MMA-αMSt-St copolymer) before glutarimidization and the glutarimide cyclization rate (mass%).
[0133] (Volume average particle size (d50) of graft copolymer (B)) N,N-dimethylformamide (DMF) was added to the graft copolymer (B) and stirred for 24 hours to prepare a 1% by mass solution of the graft copolymer (B). The solution was subjected to ultrasonic dispersion treatment for about 1 hour to prepare the sample solution. The particle size distribution was measured using a light scattering particle size distribution measuring device (Beckman Coulter ...
[0134] (Composition of the Graft Layer of Graft Copolymer (B)) Methyl ethyl ketone was added to the graft copolymer (B), and the mixture was stirred at 23°C for 24 hours. The insoluble matter was separated by centrifugation for 60 minutes at -9°C and 20,000 rpm, and the mixture was allowed to stand for 30 minutes. The supernatant was separated and methanol was added to precipitate the methacrylic copolymer by-product that was not bonded to the butadiene rubber polymer (BR). This precipitate was collected and dissolved in deuterated chloroform. 1 The unit composition was determined by measuring the H-NMR spectrum. Since the unit composition of the methacrylic copolymer (M) constituting the graft layer of the graft copolymer (B) can be regarded as being identical to the unit composition of the by-product methacrylic copolymer, the unit composition of the by-product methacrylic copolymer was taken as the unit composition of the graft layer.
[0135] (Refractive index of each copolymer (n a , n b , n c ), the average refractive index of the methacrylic copolymer (n m ), |n b -n m |) The refractive index (n a ), and the refractive index (n a ), the refractive index of the graft copolymer (B) (n b ), the refractive index of the methacrylic copolymer (C) (n c ) were measured in accordance with JIS K7142, Method A. The refractive index at 23° C. for sodium D line was measured using an Abbe refractometer (Atago Co., Ltd., “NAR-3T”). In the thermoplastic resin compositions obtained in each of the Examples and Comparative Examples, the average refractive index (n m ), and |n b -n m | was requested.
[0136] (Organic disulfide compound (D) content) The content of the organic disulfide compound (D) in the organic disulfide compound-added methacrylic copolymer (AD) or in the thermoplastic resin composition was measured as follows. 2 g of the resin (composition) to be measured was dissolved in 10 mL of dichloromethane, and then 30 mL of hexane was added to cause reprecipitation. The supernatant obtained after this reprecipitation process was separated, and the solvent in the supernatant was removed by distillation under reduced pressure to cause concentration. The concentrate obtained was dissolved again in 1 mL of dichloromethane, and then 4 mL of hexane was added to cause reprecipitation. 25 μL of the supernatant obtained after this reprecipitation process was collected on a platinum board as a measurement sample, and after removing the dichloromethane, pyrolysis gas chromatography analysis was performed. An Agilent J&W Series DB-5 column (inner diameter: 0.25 mm, film thickness: 0.25 μm, length: 30.0 m) manufactured by Agilent Technologies was connected to a Shimadzu Gas Chromatograph GC-14A. The analysis was carried out under the following conditions. The content of the organic disulfide compound (D) was determined based on a calibration curve obtained from pyrolysis gas chromatography analysis of standard solutions of multiple organic disulfide compounds with different concentrations. Vaporization chamber temperature: 260℃, Column oven temperature: 100°C, Temperature profile: Heat up to 320°C at a rate of 20°C / min. → Hold at 320°C for 30 minutes.
[0137] (Haze value) Using an injection molding machine ("M-100C" manufactured by Meiki Seisakusho Co., Ltd.), the resin composition to be measured was injection molded at a cylinder temperature of 250° C. to obtain a test piece having a side length of 50 mm and a thickness of 3 mm. The haze value of this test piece was measured using a haze meter ("HM-150" manufactured by Murakami Shikisai Kenkyusho Co., Ltd.) in accordance with JIS K7361.
[0138] (1% thermogravimetric reduction temperature) Using a thermogravimetric analyzer (Shimadzu Corporation "TGA-50"), approximately 5 mg of the resin to be measured was heated from room temperature (20-25°C) to 500°C at a heating rate of 10°C / min in a nitrogen atmosphere to obtain a TG curve. The temperature at which the weight loss rate was 1% relative to the weight before heating of 100% was determined as the 1% thermal weight loss temperature.
[0139] (Heavy Deflection Temperature (HDT)) Using an injection molding machine ("M-100C" manufactured by Meiki Seisakusho Co., Ltd.), the resin (composition) to be measured was injection molded at a cylinder temperature of 250°C to obtain a test piece having a length of 80 mm, a width of 10 mm, and a thickness of 4 mm. The obtained test piece was conditioned in accordance with JIS K6712-2. The deflection temperature under load (HDT) of this test piece was measured in accordance with JIS K7191.
[0140] (Pencil hardness) Using an injection molding machine (M-100C manufactured by Meiki Seisakusho Co., Ltd.), the resin (composition) to be measured was injection molded at a cylinder temperature of 250°C to obtain test pieces with a side length of 50 mm and a thickness of 3 mm. Using a moving table pencil scratch tester (Model P manufactured by Toyo Seiki Co., Ltd.), the presence or absence of scratches was confirmed while pressing a pencil lead against the surface of each test piece at an angle of 45° and a load of 500 g or 750 g. The hardness of the pencil lead was gradually increased, and the hardness of the lead one level softer than the point at which the scratch occurred was taken as the pencil hardness.
[0141] (Charpy impact strength) Using an injection molding machine ("M-100C" manufactured by Meiki Seisakusho Co., Ltd.), the resin (composition) to be measured was injection molded under the condition of a cylinder temperature of 250°C to obtain a test piece having a length (l) of 80 mm, a width (b) of 10 mm, and a thickness (h) of 4 mm. A notch with a tip radius (rN) of 0.25 mm and a depth of 2 mm (i.e., the remaining width (bN) of the notched test piece = 8 mm) was formed on this test piece using a notching machine in accordance with JIS K7111. The Charpy impact strength at room temperature (23°C) and / or low temperature (-30°C) was measured in accordance with JIS K7111.
[0142] [Additives] The additives used are as follows: <Organic disulfide compounds (D)> (DDS) di-tert-dodecyl disulfide.
[0143] [Production Example PE11] Production of DDS-added methacrylic copolymer (AD-1) In an autoclave equipped with a stirrer and a sampling tube, 65 parts by mass of purified methyl methacrylate (MMA), 35 parts by mass of α-methylstyrene (αMSt), 400 ppm of n-octyl mercaptan (n-OM) as a chain transfer agent, and 900 ppm of di-tert-dodecyl disulfide (DDS) were charged and mixed uniformly. 500 ppm of 2,2'-azobis(2-methylpropionitrile) (AIBN) was added as a polymerization initiator and mixed uniformly to obtain a polymerization raw material. Nitrogen gas was blown into this polymerization raw material to adjust the dissolved oxygen concentration to 3 ppm.
[0144] Next, a continuous flow tank reactor equipped with a brine cooling condenser was prepared, and the inside of the reactor was replaced with nitrogen gas. The above polymerization raw materials were continuously fed into the reactor at a constant flow rate so that the average residence time was 4.0 hours, and bulk polymerization was carried out at a polymerization temperature of 120°C, and a resin solution containing the methacrylic copolymer, which was the reaction product, was continuously discharged from the reactor. The pressure in the reactor was regulated by a pressure regulating valve connected to the brine cooling condenser. The polymerization conversion rate was 28%.
[0145] A twin-screw extruder was prepared that had a resin inlet for introducing the resin solution discharged from the reactor and a die including a resin outlet for discharging the produced resin, and further had a first vent (also called a rear vent) located relatively close to the resin inlet, a second vent (also called a front vent) located relatively close to the resin outlet, and an additive supply port located between the second vent (front vent) and the resin outlet.
[0146] The resin solution discharged from the reactor was heated using a heat exchanger and then fed into the extruder from the resin inlet. The set temperature of the heat exchanger was 200°C, and the set temperature of the cylinder of the extruder was 255°C. Volatiles mainly composed of unreacted monomers were flash evaporated from the resin solution fed into the cylinder of the extruder and discharged from the first vent (rear vent). Furthermore, the resin was transported in the axial direction of the cylinder by the screw, and the volatiles evaporated during that time were discharged from the second vent (front vent). The obtained strands were cut by a pelletizer. In this manner, pellets of DDS-added methacrylic copolymer (AD-1) were obtained. The unit composition of the copolymer, the DDS content in the DDS-added methacrylic copolymer (AD), and the results of physical property evaluation are shown in Table 1.
[0147] [Production Example PE12] Production of DDS-added methacrylic copolymer (AD-2) The charged composition was changed to 69 parts by mass of methyl methacrylate (MMA), 25 parts by mass of α-methylstyrene (αMSt), 6 parts by mass of styrene (St), 100 ppm of n-octyl mercaptan (n-OM), and 500 ppm of di-tert-dodecyl disulfide (DDS), and the average residence time was changed to 3.0 hours and the polymerization temperature to 140 ° C., but the same procedure as in Production Example PE11 was used to obtain pellets of DDS-added methacrylic copolymer (AD-2). The unit composition of the copolymer, the content of DDS in the DDS-added methacrylic copolymer (AD), and the physical property evaluation results are shown in Table 1.
[0148] [Production Example PE13] Production of DDS-added methacrylic copolymer (AD-3) The charged composition was changed to 75 parts by mass of methyl methacrylate (MMA), 15 parts by mass of α-methylstyrene (αMSt), 10 parts by mass of maleic anhydride (Mah), 200 ppm of n-octyl mercaptan (n-OM), and 300 ppm of di-tert-dodecyl disulfide (DDS), the amount of 2,2'-azobis(2-methylpropionitrile) (AIBN) was changed to 300 ppm, the average residence time was changed to 2.5 hours, and the polymerization temperature was changed to 130 ° C., but the same procedure as in Production Example PE11 was used to obtain pellets of DDS-added methacrylic copolymer (AD-3). The unit composition of the copolymer, the content of DDS in the DDS-added methacrylic copolymer (AD), and the physical property evaluation results are shown in Table 1.
[0149] [Production Example PE14] Production of DDS-added methacrylic copolymer (AD-4) The charged composition was changed to 60 parts by mass of methyl methacrylate (MMA), 23 parts by mass of α-methylstyrene (αMSt), 17 parts by mass of cyclohexylmaleimide (ChMI), 300 ppm of n-octyl mercaptan (n-OM), and 400 ppm of di-tert-dodecyl disulfide (DDS), the amount of 2,2'-azobis(2-methylpropionitrile) (AIBN) was changed to 300 ppm, the average residence time was changed to 3.0 hours, and the polymerization temperature was changed to 130 ° C., but the same procedure as in Production Example PE11 was used to obtain pellets of DDS-added methacrylic copolymer (AD-4). The unit composition of the copolymer, the content of DDS in the DDS-added methacrylic copolymer (AD), and the physical property evaluation results are shown in Table 1.
[0150] [Production Example PE15] Production of DDS-added methacrylic copolymer (AD-5) (Precursor resin manufacturing process) The charged composition was changed to 78 parts by mass of methyl methacrylate (MMA), 17 parts by mass of α-methylstyrene (αMSt), 5 parts by mass of styrene (St), 5 parts by mass of n-octyl mercaptan (n-OM) 530 ppm, and di-tert-dodecyl disulfide (DDS) 500 ppm, the amount of 2,2'-azobis(2-methylpropionitrile) (AIBN) was changed to 400 ppm, the average residence time was changed to 3.0 hours, and the polymerization temperature was changed to 140 ° C., except that pellets of DDS-added methacrylic copolymer (AD-5-Pre) (precursor resin) were obtained in the same manner as in Production Example PE11. This DDS-added methacrylic copolymer (AD-5-Pre) had a copolymer unit composition of 75% by mass of methyl methacrylate (MMA) unit / 10% by mass of α-methylstyrene (αMSt) unit / 5% by mass of styrene (St) unit, and the DDS content was 610 ppm.
[0151] (Glutarimide cyclization step) A twin-screw extruder (manufactured by Nippon Steel Corporation, "TEX30α-77AW-3V") having a transport section, a melt-kneading section, a devolatilizing section, and a discharge section, with the screw speed set to 150 rpm and the temperature set to 210 to 270 ° C., was prepared. Pellets of DDS-added methacrylic copolymer (AD-5-Pre) (precursor resin) were supplied to the transport section of this twin-screw extruder at 15 kg / hr, and an amount of monomethylamine added as an imidizing agent so that the content of methyl glutarimide (MeGI) units was the amount shown in Table 1 was injected from the additive supply port of the twin-screw extruder. In the melt-kneading section including the kneading block, the precursor resin and monomethylamine were reacted. From the obtained molten resin, by-products and excess monomethylamine were volatilized in the devolatilizing section and discharged through multiple vents. The molten resin was extruded in the form of strands from a die at the end of the twin-screw extruder, cooled in a water tank, and cut with a pelletizer to obtain pellets of DDS-added methacrylic copolymer (AD-5). The unit composition of the copolymer, the DDS content in the DDS-added methacrylic copolymer (AD), and the results of physical property evaluation are shown in Table 1.
[0152] [Production Example PE16] Production of DDS-added methacrylic copolymer (AD-6) (Precursor resin manufacturing process) The charged composition was changed to 65 parts by mass of methyl methacrylate (MMA), 28 parts by mass of α-methylstyrene (αMSt), 7 parts by mass of styrene (St), 100 ppm of n-octyl mercaptan (n-OM), and 700 ppm of di-tert-dodecyl disulfide (DDS), and the average residence time was changed to 3.0 hours and the polymerization temperature to 140 ° C., and the same procedure as in Production Example PE11 was used to obtain pellets of DDS-added methacrylic copolymer (AD-6-Pre) (precursor resin). This DDS-added methacrylic copolymer (AD-6-Pre) had a copolymer unit composition of 77% by mass of methyl methacrylate (MMA) units / 16% by mass of α-methylstyrene (αMSt) units / 7% by mass of styrene (St), and had a DDS content of 750 ppm.
[0153] (Glutarimide cyclization step) Pellets of DDS-added methacrylic copolymer (AD-6) were obtained in the same manner as in the glutarimide cyclization process of Production Example PE15, except that DDS-added methacrylic copolymer (AD-6-Pre) was used as the precursor resin and the amount of monomethylamine added as the imidization agent was changed. The unit composition of the copolymer, the DDS content in the DDS-added methacrylic copolymer (AD), and the physical property evaluation results are shown in Table 1.
[0154] [Production Example PEC17] Production of methacrylic copolymer (AC-7) Pellets of a comparative methacrylic copolymer (AC-7) not containing DDS were obtained in the same manner as in Production Example PE11, except that di-tert-dodecyl disulfide (DDS) was not used. The unit composition of the copolymer, the content of DDS in the methacrylic copolymer (AC), and the results of physical property evaluation are shown in Table 1.
[0155] [Production Example PEC18] Production of methacrylic copolymer (AC-8) Pellets of a comparative methacrylic copolymer (AC-8) (methyl methacrylate-styrene-cyclohexylmaleimide-phenylmaleimide copolymer, MMA-St-ChMI-PhMI copolymer) not containing DDS were obtained in the same manner as in Reference Example 1 of Patent Document 2 listed in the [Background Art] section, except for adjusting the mass ratio of the charged monomers. The unit composition of the copolymer, the content of DDS in the methacrylic copolymer (AC), and the results of physical property evaluation are shown in Table 1.
[0156] [Production Example PE21] Production of Graft Copolymer (B-1) A latex containing 31.5 kg of polybutadiene particles (particle diameter 0.34 μm) in terms of solid content was charged into a 200 L autoclave equipped with a stirrer, 98 kg of pure water was added, and the temperature was raised to 50° C. under a nitrogen stream while stirring. Next, 2 kg of an aqueous solution in which 1.25 g of ferrous sulfate, 2.5 g of sodium ethylenediaminetetraacetate, and 100 g of sodium formaldehyde sulfoxylate dihydrate (Rongalit) were dissolved in the pure water was added, and the mixture was stirred and mixed. Next, a monomer mixture consisting of 15.4 kg of methyl methacrylate (MMA), 5.7 kg of styrene (St), 7.4 kg of acrylonitrile (AN), and 60 g of t-dodecyl mercaptan, and 8 kg of a dispersion in which 450 g of potassium oleate was dissolved in pure water and 120 g of diisopropylbenzene hydroperoxide was dispersed, were continuously dropped into this solution with stirring using separate dropping pumps over a period of 6 hours. After the addition of these, the temperature of the reaction solution was raised to 70°C, and 30 g of diisopropylbenzene hydroperoxide was added, and the mixture was maintained for 2 hours with stirring to complete the polymerization. An antioxidant was added to the obtained latex, and the mixture was diluted with pure water at room temperature (10 to 30° C.) to a solid content of 15% by mass, and then the temperature was raised to 60° C. Dilute sulfuric acid was added with vigorous stirring to perform salting out, and the temperature was raised to 90° C. to coagulate the mixture, which was then dehydrated, washed with water, and dried to obtain a powdered graft copolymer (B-1). The obtained graft copolymer (B-1) is a core-shell type graft copolymer particle in which at least a part of the surface of a core particle made of a polybutadiene particle is covered with a shell layer (graft layer) made of a methacrylic copolymer, and has a refractive index (n b The molecular weight distribution of the graft layer was 54% by mass of methyl methacrylate (MMA) units / 20% by mass of styrene (St) units / 26% by mass of acrylonitrile (AN) units, and the volume average particle size (d50) was 0.36 μm.
[0157] [Production Example PE22] Production of Graft Copolymer (B-2) A powdery graft copolymer (B-2) was obtained in the same manner as in Production Example PE21, except that the monomer mixture was changed to a monomer mixture consisting of 22.2 kg of methyl methacrylate (MMA), 6.3 kg of styrene (St), and 60 g of t-dodecyl mercaptan. The obtained graft copolymer (B-2) is a core-shell type graft copolymer particle in which at least a part of the surface of a core particle made of a polybutadiene particle is covered with a shell layer (graft layer) made of a methacrylic copolymer, and has a refractive index (n b ) was 1.518, the composition of the graft layer was 78 mass % of methyl methacrylate (MMA) units / 22 mass % of styrene (St) units, and the volume average particle size (d50) was 0.36 μm.
[0158] [Production Example PE23] Production of graft copolymer (B-3) A latex containing 36 kg of styrene-butadiene copolymer particles (styrene unit / butadiene unit (mass ratio) = 30 / 70, particle diameter 0.30 μm) in terms of solid content was charged into a 200 L autoclave equipped with a stirrer, pure water was added, and the temperature was raised to 50°C under a nitrogen stream while stirring. The total amount of water in the latex and the amount of pure water added was 100 kg. Next, 2 kg of an aqueous solution in which 1.8 g of ferrous sulfate, 3.6 g of sodium ethylenediaminetetraacetate, and 108 g of sodium formaldehyde sulfoxylate dihydrate (Rongalit) were dissolved in the pure water was added, and the mixture was stirred and mixed. Next, a monomer mixture consisting of 13.2 kg of methyl methacrylate (MMA), 10.8 kg of styrene (St), and 240 g of t-dodecyl mercaptan, and 8 kg of a dispersion in which 450 g of potassium oleate was dissolved in pure water and 48 g of diisopropylbenzene hydroperoxide was dispersed, were continuously dropped into this solution with stirring using separate dropping pumps over a period of 6 hours. After the addition of these, the temperature of the reaction solution was raised to 70°C, and 24 g of diisopropylbenzene hydroperoxide was added, and the mixture was maintained for 2 hours with stirring to complete the polymerization. An antioxidant was added to the obtained latex, and the mixture was diluted with pure water at room temperature (10 to 30° C.) to a solid content of 15% by mass, and then the temperature was raised to 70° C. Dilute sulfuric acid was added with vigorous stirring to perform salting out, and the temperature was raised to 95° C. to coagulate the mixture, which was then dehydrated, washed with water, and dried to obtain a powdered graft copolymer (B-3). The obtained graft copolymer (B-3) is a core-shell type graft copolymer particle in which at least a part of the surface of a core particle made of a styrene-butadiene copolymer particle is covered with a shell layer (graft layer) made of a methacrylic copolymer, and has a refractive index (n b ) was 1.540, the composition of the graft layer was 55 mass % of methyl methacrylate (MMA) units / 45 mass % of styrene (St) units, and the volume average particle size (d50) was 0.35 μm.
[0159] [Production Example PE31] Production of methacrylic copolymer (C-1) A methyl methacrylate-styrene-acrylonitrile copolymer (MMA-St-AN) was polymerized as a methacrylic copolymer (C-1) in the same manner as in Reference Examples 1 to 4 of JP-A-7-324153, except that the mass ratio of the charged monomers was adjusted. The obtained copolymer had a unit composition of 54 mass% methyl methacrylate (MMA) unit / 20 mass% styrene (St) unit / 26 mass% acrylonitrile (AN) unit, a weight average molecular weight (Mw) of 84,000, a glass transition temperature (Tg) of 101° C., a refractive index (n c ) was 1.517.
[0160] [Production Example PE32] Production of methacrylic copolymer (C-2) A methyl methacrylate-styrene copolymer (MMA-St copolymer) was polymerized as a methacrylic copolymer (C-2) in the same manner as in Experimental Example (B)-1 of Patent Document 3 cited in the [Background Art] section, except for adjusting the mass ratio of the charged monomers. The obtained copolymer had a unit composition of 75 mass% methyl methacrylate (MMA) units / 25 mass% styrene (St) units, a weight average molecular weight (Mw) of 115,000, a glass transition temperature (Tg) of 104°C, a refractive index (n c ) was 1.520.
[0161] [Examples E1 to E9, Comparative Examples EC1 to EC7] In each of Examples E1 to E9 and Comparative Examples EC1 to EC6, DDS-added methacrylic copolymer (AD) or comparative methacrylic copolymer (AC), graft copolymer (B), and methacrylic copolymer (C) were blended in the composition shown in Table 2 or Table 3, and melt-kneaded and extruded at 245°C using a twin-screw extruder with L / D=32.5 and a shaft diameter of 62.5 mmφ to obtain a thermoplastic resin composition (R) or (RC). Note that L / D is the ratio of the effective length (L) of the screw to the diameter (D) of the screw. The evaluation results are shown in Tables 2 and 3. In these tables, conditions not shown in the tables were common conditions.
[0162] [Table 1]
[0163] [Table 2]
[0164] [Table 3]
[0165] [Summary of results] All of the DDS-added methacrylic copolymers (AD) obtained in Production Examples PE11 to PE16 contained an appropriate amount of the organic disulfide compound (D) and had good heat resistance, thermal decomposition resistance (thermal stability), surface hardness, and impact resistance at room temperature. In Examples E1 to E9, a thermoplastic resin composition was obtained containing 10 to 95 mass% of a DDS-added methacrylic copolymer (AD) containing a first methacrylic copolymer (A) and an organic disulfide compound (D), 5 to 40 mass% of a graft copolymer (B), 0 to 85 mass% of a methacrylic copolymer (C), and 1 to 1000 ppm of an organic disulfide compound (D). All of the thermoplastic resin compositions obtained in these Examples contained the DDS-added methacrylic copolymer (AD) having the above-mentioned properties, and therefore had good heat resistance, surface hardness, and impact resistance at room temperature.
[0166] It is believed that the thermoplastic resin compositions obtained in these examples all contain an appropriate amount of organic disulfide compound (D), which suppresses thermal decomposition of the first methacrylic copolymer (A) and the second methacrylic copolymer (C) which may be contained as an optional component, thereby improving heat resistance and thermal decomposition resistance (thermal stability). In all of the thermoplastic resin compositions obtained in the examples, the gelation of the graft copolymer (B) during the production of the thermoplastic resin composition and the molded article was suppressed by containing an appropriate amount of the organic disulfide compound (D). As a result, all of the obtained thermoplastic resin compositions had good impact resistance at low temperatures (below freezing point).
[0167] In all of the thermoplastic resin compositions obtained in these Examples, the refractive index difference (|n b -n m |, Δn) was 0.01 or less. The thermoplastic resin compositions obtained in these Examples had reduced light scattering at the boundary between the matrix resin and the rubber component, and had good transparency.
[0168] In Comparative Examples EC1 and EC2, a thermoplastic resin composition was obtained that did not contain the first methacrylic copolymer (A) and the organic disulfide compound (D). The thermoplastic resin compositions obtained in these Comparative Examples had low heat resistance and surface hardness. The thermoplastic resin composition obtained in Comparative Example EC2 also had low impact resistance at low temperatures. In Comparative Example EC3, a thermoplastic resin composition containing more than 40 mass % of the graft copolymer (B) was obtained. The obtained thermoplastic resin composition had low heat resistance and surface hardness.
[0169] The comparative methacrylic copolymer (AC-7) obtained in Production Example PEC17 had low resistance to thermal decomposition because the organic disulfide compound (D) was not added to the polymerization raw materials. In Comparative Example EC4, a thermoplastic resin composition was obtained that contained the comparative methacrylic copolymer (AC-7) and did not contain the organic disulfide compound (D). The obtained thermoplastic resin composition had low heat resistance and low impact resistance at low temperatures.
[0170] The comparative methacrylic copolymer (AC-8) obtained in Production Example PEC18 had improved heat resistance by increasing the content of maleimide units, but its impact resistance was reduced. In Comparative Example EC5, a thermoplastic resin composition was obtained that contained the comparative methacrylic copolymer (AC-8) and did not contain the organic disulfide compound (D). The obtained thermoplastic resin composition had low impact resistance at room temperature and low temperature.
[0171] The thermoplastic resin composition obtained in Comparative Example EC6 had a refractive index difference (|n b -n m |, Δn) exceeded 0.01, and the transparency was low.
[0172] The present invention is not limited to the above-described embodiment and examples, and appropriate design changes are possible without departing from the spirit of the present invention.
Claims
1. 10 to 95% by mass of a first methacrylic copolymer (A) which is composed of 10 to 99% by mass of methyl methacrylate units, 1 to 40% by mass of one or more isopropenyl aromatic compound units (UI), and 0 to 60% by mass of one or more other units (UO) and has a glass transition temperature of 120 to 150° C.; 5 to 40% by mass of a graft copolymer (B) obtained by graft copolymerizing a butadiene-based rubber-like polymer (BR) containing 60 to 100% by mass of butadiene units with a methacrylic copolymer (M) containing 10 to 90% by mass of methyl methacrylate units, 90 to 10% by mass of aromatic vinyl compound units, and 49 to 0% by mass of vinyl cyanide compound units; 0 to 85% by mass of a second methacrylic copolymer (C) containing 10 to 90% by mass of methyl methacrylate units, 70 to 10% by mass of aromatic vinyl compound units other than isopropenyl aromatic compound units, and 49 to 0% by mass of vinyl cyanide compound units; and an organic disulfide compound (D) of 1 to 1000 ppm, A thermoplastic resin composition satisfying the following formula (1): 0≦|n b -n m |≦0.01・・・(1) In the above formula, n m is defined by the following formula (2). n m =(n a ×w a +n c ×w c ) / (w a +w c )・・・(2) In the above formula, n a , n b , n c are the refractive indices of the first methacrylic copolymer (A), the graft copolymer (B), and the second methacrylic copolymer (C) at 23° C. for the sodium D line. a , W b , W c are the mass ratios of the first methacrylic copolymer (A), the graft copolymer (B), and the second methacrylic copolymer (C) to the total mass of the first methacrylic copolymer (A), the graft copolymer (B), and the second methacrylic copolymer (C) in the thermoplastic resin composition, respectively. a +w b +w c = 1.
2. The thermoplastic resin composition of claim 1, wherein the one or more isopropenyl aromatic compound units (UI) comprise α-methylstyrene units.
3. The thermoplastic resin composition according to claim 1, wherein the first methacrylic copolymer (A) contains, as the other units (UO), aromatic vinyl compound units other than isopropenyl aromatic compound units.
4. The thermoplastic resin composition according to any one of claims 1 to 3, wherein the first methacrylic copolymer (A) contains, as the other units (UO), one or more ring structure units (UR) selected from the group consisting of an acid anhydride unit, an imide unit having a ring structure, and a lactone ring unit.
5. 2. The thermoplastic resin composition according to claim 1, wherein the butadiene-based rubbery polymer (BR) is one or more rubbery polymers selected from the group consisting of polybutadiene, copolymers containing butadiene units and aromatic vinyl compound units, and hydrogenated products thereof.
6. The thermoplastic resin composition according to claim 1, wherein the graft copolymer (B) is a core-shell type graft copolymer particle in which at least a part of the surface of a core particle made of a butadiene-based rubber-like polymer (BR) is covered with a shell layer made of a methacrylic copolymer (M).
7. The thermoplastic resin composition of claim 1, wherein the one or more organic disulfide compounds (D) comprise di-tert-dodecyl disulfide (DDS).
8. The thermoplastic resin composition according to claim 1, wherein a haze value of a 3 mm thick flat plate made of the thermoplastic resin composition, measured in accordance with JIS K7136, is 0 to 10%.
9. The thermoplastic resin composition according to claim 1, wherein a test piece made of the thermoplastic resin composition and having a length of 80 mm, a width of 10 mm and a thickness of 4 mm has a deflection temperature under load of 85 to 120°C, as measured in accordance with JIS K7191.
10. A test piece made of the thermoplastic resin composition and having a length of 80 mm, a width of 10 mm, and a thickness of 4 mm is provided with a notch having a tip radius of 0.25 mm and a depth of 2 mm, and the Charpy impact strength measured at -30°C in accordance with JIS K7111 is 4 to 15 kJ / m 2 The thermoplastic resin composition according to claim 1 ,
11. A step (S1) of producing an organic disulfide compound-added methacrylic copolymer (AD) containing a first methacrylic copolymer (A) and an organic disulfide compound (D); and (S2) melt-kneading 10 to 95% by mass of the organic disulfide compound-added methacrylic copolymer (AD), 5 to 40% by mass of the graft copolymer (B), and 0 to 85% by mass of the second methacrylic copolymer (C).
12. A molded article comprising the thermoplastic resin composition according to claim 1.
Citation Information
Patent Citations
transparent thermoplastic resin composition
JP1993279547A
Transparent, heat-resistant, thermoplastic resin composition
JP2001294722A
Transparent rubber-modified styrenic resin composition and molding of the same
JP2013104042A
Cited By
Thermoplastic resin composition, molded article, and film
WO2026121206A1